Method for degumming silk fibres
By incubating silk fibers with hydroxide, the sericin glue layer was removed, combined with confocal microscopy and staining determination technology, the fiber cross-sectional area and volume were accurately measured, and the problem of inaccurate determination of the mechanical properties of silk fibers in the prior art was solved. , and the effect of efficient removal of glue layer and mechanical properties is achieved.
Patent Information
- Application Number
- CN202380046499.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-16
- Filing Date
- 2023-06-15
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art tends to cause thermal damage to the protein components when removing the glue layer of the silk fibers, and it is difficult to accurately determine the mechanical properties of the silk fibers, especially considering the asymmetry and defects of the fibers.
A non-thermal saving preparation to remove sericin glue layer was developed, and silk fibers were incubated with hydroxides to retain the integrity and secondary structure of silk fibroin, improving the mechanical properties and thermal stability of the fibers. At the same time, confocal microscopy and staining measurement methods were used to accurately measure the cross-sectional area and volume of the fibers to determine their true mechanical properties.
The glue layer of the silk fiber is effectively removed, which improves the Young's modulus and tensile strength of the fiber, improves thermal stability, and obtains soluble silk fibroin with high purity and rheological characteristics similar to natural silk. At the same time, the mechanical properties of the silk fibers were accurately determined, taking into account the asymmetry and defects of the fibers.
Smart Images

Figure BDA0005182823020000101 
Figure BDA0005182823020000171 
Figure BDA0005182823020000231
Abstract
Description
Field of the Invention
[0001] The present invention relates to a method for degumming silk fibers and for obtaining high-quality silk fibroin solutions. The present invention also provides silk fibers and reconstructed silk soluble forms. The present invention also relates to a method for accurately and precisely determining the mechanical properties of biological fibers such as silk fibers.
[0002] background
[0003] Natural silk fibroin fibers represent a class of protein building blocks that can be further functionalized and / or reprocessed into many different material forms. The standard method for determining the specific mechanics of silk fibroin fibers involves removing the gum coating layer called sericin by boiling the fibers in an aqueous solution containing Na2CO3, and further analyzing and calculating the mechanics by applying the shape approximation of a perfect cylinder. However, such an approach is not ideal for protecting the protein (fibroin) component from thermal damage after the removal of the glue and for inferring the correct mechanics of silk fibers, which are not perfectly cylindrical in shape but asymmetrical with multiple defects, a common phenomenon in biological fibers.
[0004] Overview
[0005] In one embodiment, the present invention relates to the development of a formulation for non-thermal sparing removal of sericin glue layers that preserves fibroin protein integrity, secondary structure and thus improves fiber mechanics and thermal stability of protein materials. When the fibers are further redissolved, the method also enables the acquisition of soluble silk of high purity and rheological properties comparable to those of native silk (i.e., silk extracted directly from silk glands via dissection).
[0006] In addition and in one embodiment, the present invention establishes a novel method for determining the mechanical properties of silk fibers, which takes into account the asymmetry and internal / external defects of the fibers. The developed method is not only beneficial for producing silk-based materials with customized and enhanced properties, but also for correctly establishing the mechanical properties of asymmetric fiber materials made of natural and synthetic components. The present invention establishes a new method for determining the "real" mechanical properties of biological fibers like silk, which takes into account the asymmetry and the presence of defects of the fibers.
[0007] In one embodiment, the present invention provides a method for removing at least a portion of a glue layer from a silk fiber, the method comprising: incubating the silk fiber in an incubation medium, the incubation medium comprising a hydroxide. In one embodiment, the present invention provides a method for removing at least a portion of a glue layer from a silk fiber, the method comprising: incubating the silk fiber in an incubation medium, the incubation medium comprising a hydroxide; wherein the method is performed at a temperature in the range between 5 degrees Celsius and 60 degrees Celsius. In one embodiment, the incubation medium consists of a hydroxide and water. In one embodiment, the incubation of the disclosed method consists of a single incubation step.
[0008] In one embodiment, the method is carried out at a temperature in the range between 5 degrees Celsius and 60 degrees Celsius. In one embodiment, the hydroxide is selected from: NaOH, LiOH, KOH, RbOH, CsOH, Ca(OH)2, Sr(OH)2 or Ba(OH)2 or a combination thereof. In one embodiment, the concentration of the hydroxide in the incubation medium is in the range between about 0.1M and 1M. In one embodiment, the incubation medium also comprises at least one buffer. In one embodiment, the incubation medium also comprises at least one salt. In one embodiment, the incubation is carried out between 1 minute and 60 minutes. In one embodiment, the method also includes rinsing the silk fibers in the liquid after incubation. In one embodiment, the liquid includes water or a solution. In one embodiment, the method also includes drying the silk fibers after rinsing in the liquid. In one embodiment, the method also includes separating the silk fibers into individual fibers.
[0009] In one embodiment, the present invention provides a degummed silk fiber comprising a core and a glue layer, wherein the glue layer constitutes 0% to 20% of the cross-sectional area of the degummed silk fiber.
[0010] In one embodiment, the degummed silk fibers exhibit a Young's modulus of at least about 10 GPa. In one embodiment, the degummed silk fibers exhibit a Young's modulus that is at least 1.5 times greater than that of untreated silk fibers. In one embodiment, the degummed silk fibers exhibit a tensile strength of at least about 400 MPa. In one embodiment, the degummed silk fibers exhibit a tensile strength that is at least 1.25 times greater than that of untreated silk fibers. In one embodiment, the degummed silk fibers exhibit a breaking strain of at least about 0.2. In one embodiment, the degummed silk fibers exhibit a Weibull characteristic strength parameter (α) of at least about 400 MPa.
[0011] In one embodiment, the degummed silk fibers exhibit a Weibull characteristic intensity parameter (α) that is at least 1.2 times greater than that of untreated silk fibers. In one embodiment, the degummed silk fibers exhibit a Weibull shape parameter (β) of at least about 4. In one embodiment, the degummed silk fibers are produced by a method as described above.
[0012] In one embodiment, the present invention provides a reconstructed silk fibroin material, the material comprising silk fibroin and a liquid, the silk fibroin being derived from degummed silk fibers as described above. In one embodiment, the liquid comprises water. In one embodiment, the liquid comprises a buffer.
[0013] In one embodiment, the present invention provides a method for determining the average mechanical properties of more than one asymmetric fiber, the method comprising:
[0014] a) obtaining more than one cross-sectional image along the length of one of the asymmetric fibers using a confocal microscope;
[0015] b) Calculate the cross-sectional area of the asymmetric fiber;
[0016] c) calculating the average cross-sectional area along the length of the asymmetric fiber;
[0017] d) measuring the extension of the asymmetric fiber relative to the load until the asymmetric fiber breaks;
[0018] e) using the average cross-sectional area to obtain stress-strain diagrams for asymmetric fibers;
[0019] f) Obtaining the maximum strength and Young's modulus from the stress-strain diagram of the asymmetric fiber;
[0020] g) performing stages 'a' to 'f' on more than one asymmetric fiber to obtain more than one stress / strain data set; and
[0021] h) Calculate the average maximum strength and average Young's modulus of more than one asymmetric fiber.
[0022] In one embodiment, the asymmetric fibers are dyed with a dye prior to step (a). In one embodiment, the asymmetric fibers are of biological origin. In one embodiment, the asymmetric fibers are degummed. In one embodiment, the asymmetric fibers are coated with an additional material.
[0023] In one embodiment, the method further comprises utilizing a two-parameter Weibull distribution, comprising:
[0024] a) rank the maximum intensity of more than one stress / strain data set from lowest to highest and assign a number to the data set;
[0025] b) calculating the natural logarithm of the maximum intensity of each data set;
[0026] c) Calculate the failure probability f(σ) of each data set;
[0027] d) Plot the natural logarithm of the maximum intensity versus ln(-ln(1-f(σ)); and
[0028] e) From the graph of 'd', the shape parameter β is extracted from the gradient and the scale parameter α is extracted from α=exp(intercept / β).
[0029] In one embodiment, the asymmetric fibers are dyed with a dye prior to step (a). In one embodiment, the asymmetric fibers are of biological origin. In one embodiment, the asymmetric fibers are degummed. In one embodiment, the asymmetric fibers are coated with an additional material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] For a better understanding of the subject matter disclosed herein and for the purpose of illustrating how the same may be implemented in practice, embodiments will now be described, by way of non-limiting examples only, with reference to the accompanying drawings, in which:
[0032] Figures 1A to 1D Shown is a representation of microscopic analysis of degummed silk fibers obtained using different degumming methods.
[0033] FIG. 1E to FIG. 1I Microscopic analysis of degummed RSF fibers obtained by using different degumming methods is shown. Untreated fibers ( Figure 1E ) and degummed fibers ( Figure 1F :Na2CO3, Figure 1G :NaOH 0.1M, Figure 1H : NaOH 0.5M and Fig. 1I : NaOH 1 M). The fibers were stained with Nile red dye, wherein the longitudinal 3D confocal image is shown on the left and the longitudinal 3D confocal processed image is shown on the right.
[0034] FIG. 2 shows the analysis of the mechanical behavior of the produced silk and degummed silk fibroin fibers. Figure 2A Represents the cross-sectional distribution. Figure 2B The true stress-strain curves for untreated silk fibers and degummed silk fibers are shown, and the graphical representations of the 'true' mechanical properties are as follows: Figure 2C The true strain is shown in Figure 2D The true Young's modulus is shown in Figure 2E The true tensile strength is shown in Figure 2F A graphical representation of a two-parameter Weibull distribution plot showing the calculation of the true value of the strength for different fibers.
[0035] Figure 3 is a representation of the thermogravimetric analysis (TGA) of the fibers before and after different degumming treatments.
[0036] Figure 4 shows the structural characteristics and mechanism of silk fiber degumming.
[0037] Figure 5 Schematic diagram representing different degumming treatments and processes.
[0038] FIG6 graphically illustrates a synergistic analysis of measured cross-sectional areas of untreated fibers, fibers degummed via a standard method, and silk fibroin fibers treated with a NaOH-based solution.
[0039] FIG. 7 depicts SEM images of NaOH 1M treating microscale fibers and breaking them down into individual nanofibrils.
[0040] FIG8 shows an untreated silk fiber ( Fig. 8A ), Na2CO3 treated silk fibers ( Figure 8B ), silk fibers treated with 0.1M NaOH ( Figure 8C ), silk fibers treated with 0.5M NaOH ( Fig.8D ) and NaOH 1M treated silk fibers ( Fig. 8E )’s stress-strain curve.
[0041] FIG. 9 is a representation of the thermogravimetric analysis (TGA) of the fibers before and after different degumming treatments. Fig.9A It is for untreated silk fibers. Fig. 9B This is for silk fibers treated with 0.1M NaOH. Fig. 9C This is for silk fibers treated with NaOH 1M.
[0042] Figure 10 shows TGA analysis of the fiber before and after different degumming treatments. Five TGA scan repetitions were performed on the degummed silk fibroin fiber, showing the beginning of the TGA analysis of the degummed fiber using NaOH. Fig. 10A Dynamic Mechanical Analysis (DMA) of the degummed fibers is shown; the storage modulus is represented by the solid line and the loss modulus is represented by the dashed line. Fig. 10B The glass transition temperature of the debonded fibers is shown.
[0043] FIG. 11 shows the properties related to the structural characteristics and mechanisms of soluble silk fibroin. Fig.11ASmall angle X-ray scattering (SAXS) analysis of soluble silk fibroin is shown; azimuthally-interacted background-subtracted solution X-ray scattering absolute intensity I as a function of the magnitude of the scattering vector q for native silk and soluble RSF obtained from different degumming methods. Fig. 11B and Fig. 11C Rheological analysis showing the change in viscosity in response to applied shear, where the shear rate changes from 0.1 s -1 Increase to 500s -1 and from 500s -1 Back to 0.1s -1 The following samples were analyzed: native silk fibroin solution obtained from silkworm glands via dissection, RSF solution obtained via chemical redissolution of degummed silk fibers in the presence of Na2CO3, NaOH 0.1 M, and NaOH 0.5 M and NaOH 1 M. The shaded colors represent standard deviations (mean ± sd, n ≥ 3).
[0044] Fig.12 The algorithm description of the cross-sectional analysis process completed by Matlab script is shown. First (first step), the 3D confocal images of two channels are taken, and then (second step), the image is post-processed by Imaris program. In the third step, the image of two channels is converted into binary images (binary images) by the script, and then the cross-sectional area of each pixel along the silk fiber (axis) is collected.
[0045] Fig.13 Statistical analysis of the mechanical measurements is shown. A one-way analysis of variance (ANOVA) was performed between all samples to determine if there were significant differences between the means. Differences between groups were statistically significant at p<0.05.
[0046] FIG14 shows Fourier transform infrared spectroscopy (FTIR) analysis of degummed silk fibers and untreated silk fibers. Untreated silk fibers ( Fig.14A ), Na2CO3 treated silk fibers ( Fig. 14B ), silk fibers treated with 0.1M NaOH ( Fig. 14C ), silk fibers treated with 0.5M NaOH ( Fig.14D ) and NaOH 1M treated silk fibers ( Fig.14E )’s FTIR spectrum. Fig.14F Shown at 1610cm -1 -1635cm-1 β-sheet at 1690 cm -1 -1705cm -1 The antiparallel β-sheet at 1635 cm -1 -1665cm -1 The random coil and α-helix at 1665 cm -1 -1690cm -1 Bar graph of the relative amount of β-turns at .
[0047] Details
[0048] In addition to the traditional textile industry, natural silkworm cocoon fibroin from silkworms (Bombyx mori) (B. mori) is widely used in various biomedical applications. FDA-approved B. mori silk fibroin is used as a multifunctional biomaterial in the form of films, membranes, gels, sponges, powders, scaffolds and nanoparticles. Such popularity has been achieved due to its excellent mechanical properties, controlled porosity, oxygen and water permeability, biodegradability, hemostatic properties, non-cytotoxicity, low antigenicity and non-inflammatory properties. In order to utilize these excellent properties, a pretreatment in the form of separation is required between the silk fibroin core component and the sericin gel coating layer. The fraction of the sericin layer varies between 25%-30% of the total fiber weight. The silk fibroin core fiber is characterized by a highly hierarchical structural organization. The silk fibroin core fiber, which accounts for 70%-75% of the silk fiber, is made of two microscale fibers with a diameter of ~10 μm each, wherein a single silk fibroin fiber contains an arranged bundle of silk fibroin nanofibrils. Nanofibrils are made of self-assembled fibroin. Fibroin itself is a large globular protein of size ~400kDa-450kDa, which comprises two subunits of heavy chain and light chain, which are connected via a single disulfide bond. The structural organization of protein in a single nanofibril alternates between crystalline and disordered regions, and the score of the crystalline region defines the strength of the final fiber. The overall mechanics of silk fiber is to transform the soluble fibroin stored in the gland (silk raw material) from a relatively disordered state (random coil conformation) structure into a highly ordered solid fiber evolution rich in β-sheets via a spinning process.
[0049] Traditionally, the sericin layer is removed by boiling the silk fibers in an aqueous solution containing Na2CO3 for about one hour. Such a procedure usually damages the silk fibroin components by changing their folding or by separating between the heavy chain protein subunits and the light chain protein subunits. Such damage reduces the mechanical properties of the silk fibroin fibers. In addition, it affects the thermal stability of the silk fibroin fibers and further reduces the quality of the reconstructed silk fibroin (RSF) obtained via chemical redissolution.
[0050] In one embodiment, the present invention provides a process for gently removing the glue layer from silk fibers without causing thermal damage. The process of the present invention retains the protein secondary structure and its crystallinity. In addition, the process improves the mechanical properties and thermal stability of the fiber. In addition, and in one embodiment, when the silk fibroin fiber treated by the process of the present invention is chemically redissolved to obtain an aqueous solution of RSF, the rheological properties of the resulting RSF are comparable to those of native silk from silkworm glands.
[0051] To improve the mechanical properties of silk fibroin fibers, the present disclosure shows a formulation that effectively removes the sericin glue layer at room temperature and preserves the structural hierarchy of the silk material, including the molecular structure of silk fibroin, the nanostructure of silk fibroin nanofibrils, and thus the integrity of the final silk fibroin microfibrils. Accurate analysis of mechanical properties is achieved by determining the actual initial cross-sectional area of asymmetric silk fibers. As shown herein, removing the sericin layer with the developed formulation improves the Young's modulus (96% and 23%) and strength (52% and 47%) of the fiber, respectively, compared to untreated fibers and boiled fibers, without affecting its strain. In addition, the treatment produces a lower variation in defects present along the fiber. The developed method is not only beneficial for the production of silk-based materials with customized properties, but also for establishing the mechanical properties of asymmetric fiber biomaterials made from natural components.
[0052] In the invention disclosed herein, a simple method based on sodium hydroxide (NaOH) for gentle removal of sericin layer without thermal damage to the protein fiber core is provided. NaOH is used in many protein extraction protocols to dissolve impurities, minerals, pigments and specific proteins. In order to disrupt the non-covalent interactions between proteins and remove the sericin layer by NaOH, conditions such as temperature, NaOH concentration and time of exposure to NaOH are considered. Compared with untreated silkworm fibers and boiled fibers boiled in standard Na2CO3-containing solutions, the silk fiber treatment of the present disclosure retains the secondary structure and crystallinity of the silk fibroin component, protects the morphology of the fibers and improves the mechanics and stability of the fibers. When the silk fibroin fibers are further chemically redissolved to obtain an aqueous protein raw material (reconstructed silk fibroin (RSF)), the rheological properties of the RSF are comparable to those of natural silk extracted from silkworm glands. It is worth noting that since aqueous silk is defined as a flow-sensitive material, the rheological properties of silk play an important role in the production of silk fibers via spinning. Thus, "improving" the rheological properties of RSF improves the production of artificial silk fibers, gels or films with customized mechanical properties. In addition, a new method for determining the actual initial cross-sectional area of silk fibroin fibers is shown herein. The correct determination of the cross-sectional area is generally used as the basis for calculating the strength of biological and non-biological fibers. The method disclosed herein includes a staining assay that can distinguish between the two main components of silk fibers, namely silk fibroin and sericin gel. The method facilitates the extraction of volume parameters and cross-sectional area parameters of non-uniform fibers from confocal microscopy analysis, which are further used for the comprehensive analysis of the mechanical properties of the fibers. The procedure takes into account the asymmetric shape of the fiber. The two-parameter Weibull distribution is able to analyze the presence of defects along the fiber surface morphology, thereby correctly understanding the mechanical properties of silk fibroin fibers.
[0053] Silk fibroin fibers represent a class of protein building blocks that can be further functionalized and / or reprocessed into different material forms. The standard method for determining the specific mechanics of these fibers involves removing the sericin glue coating by boiling the fibers in the presence of Na2CO3, and further analyzing and calculating the mechanics by applying the shape approximation of a perfect cylinder. However, such methods are not ideal for protecting the protein (fibroin) component from thermal damage during glue removal and for inferring the mechanics of the correct and "real" silk fiber, the natural shape of which is asymmetric and has multiple defects, which is a common phenomenon in biological fibers. Disclosed herein is a formulation for non-thermal economical removal of the sericin glue layer, which retains the integrity of the fibroin, its secondary structure and thus improves fiber mechanics and fiber stability. The method has been proven and is able to obtain soluble silk proteins with high purity and rheological properties similar to those of natural silk raw materials originally stored in animal silk glands. Secondly, a new method for determining the correct mechanical (or 'real') properties of silk fibers takes into account the asymmetry of the fiber and the presence of multiple defects. The developed method is beneficial not only for generating silk-based materials with tailored properties, but also for establishing the mechanical properties of asymmetric fibrous biomaterials made from natural and synthetic building blocks.
[0054] As mentioned herein, "real" about silk fiber and its related properties refers to the characteristic considered due to the natural asymmetric shape of silk fiber, and may contain defects. In some embodiments, silk fiber comprises at least one defect. In some embodiments, silk fiber structure is asymmetric. Therefore, the term "real" illustrates that silk fiber is a non-idealized structure, such as a uniform tube, but includes the fact of multiple structural elements. Such structural elements may include defects, multilayer structures and asymmetry, or any other inhomogeneous internal structure. It is possible to determine the total cross-sectional area of silk fiber and therefore determine that its volume allows calculation of true mechanical properties.
[0055] In some embodiments, the glue layer in the silk comprises sericin. In some embodiments, the glue layer comprises a protein-based structure. In some embodiments, the glue layer is referred to as the "outer layer" of the silk fiber. In some embodiments, the glue layer is referred to as the "coat" or "coating" layer of the silk fiber or is referred to as a "shell". In some embodiments, the "outer layer" comprises any material that is not based on fibroin. In some embodiments, the outer layer comprises glycoprotein. In some embodiments, the outer layer comprises lipids. In some embodiments, the glue layer surrounds the inner fiber of fibroin. In one embodiment, the glue layer surrounds a portion of the fibroin fiber. In one embodiment, the glue layer surrounds at least a portion of two fibroin fibers.
[0056] In one embodiment, the present invention provides a novel method for evaluating silk mechanics. Currently, fiber mechanics calculations rely on the perfect cylindrical shape approximation of the fiber. However, the cross-section of the silk fiber presents a non-uniform and non-cylindrical shape, and there are multiple defects. The inaccuracy of the shape approximation greatly changes the tensile strength value and the fiber strength. In one embodiment, the method of the present invention provides an accurate and precise procedure for determining fiber mechanics. According to this aspect and in one embodiment, the method of the present invention utilizes the accurate cross-section of the fiber to measure, for example, tensile strength. In one embodiment, in order to find the accurate cross-section of the fiber, a staining assay is used. In one embodiment, the staining assay enables the distinction between silk fiber components, such as fibroin and sericin. In one embodiment, a microscope is used to evaluate the cross-section of the dyed fiber. For asymmetric fibers, confocal microscopy helps to obtain cross-sectional measurements along the fiber. Therefore, the average cross-section of the cross-section of the fiber along the length of the fiber is obtained. Therefore and in one embodiment, a script is used to extract the volume parameters and cross-sectional parameters of the non-uniform fiber from the confocal microscopy analysis. In an embodiment of the present invention, the volume parameters and cross-sectional parameters are further used for the comprehensive analysis of silk fiber mechanics.
[0057] An object of the present invention is to set up the more accurate and precise method for determining the mechanical properties of silk fibers. In one embodiment, process of the present invention comprises the non-destructive removal of glue components. In some embodiments, process of the present invention also comprises a dyeing procedure to enable the differentiation between the biopolymer composite material components. In one embodiment, an analytical process is used to determine the mechanical properties of non-uniform fibers.
[0058] Development of formulations for degumming silk fibers;
[0059] In one embodiment, the present invention provides a fiber degumming method that eliminates the thermal damage caused by the standard protocol for silk fiber degumming. The standard protocol currently used involves boiling silk fibers in aqueous sodium bicarbonate (Na2CO3, 0.02M, 30min to 1 hour) at 100°C. In one embodiment, the present invention provides a detailed screening of media for fine sericin glue removal (see Table 1 for a summary of liquid solutions). Short-time incubation of silk fibers at room temperature in the presence of different molar concentration values of NaOH ranging from about 0.1M to 1M resulted in high yields of sericin removal (see Figure 5and Table 1). The sericin is initially ~30 wt% of the initial fiber weight. In one embodiment, all of the sericin layer is removed by the process of the present invention. In one embodiment, the sericin layer, which is ~30% by weight of the silk fiber, has been completely removed by the process of the present invention as described herein. In one embodiment, more than 75% of the sericin layer, which is ~30% by weight of the original silk fiber, has been removed by the process of the present invention as described herein. In one embodiment, at least 90%, or at least 95%, or at least 99%, or at least 99.9% of the weight of the sericin layer has been removed by the process of the present invention. In one embodiment, at least 90%, or at least 95%, or at least 99%, or at least 99.9% of the volume of the sericin layer has been removed by the process of the present invention.
[0060] In one embodiment, the term "a" or "one" or "an" refers to at least one. In one embodiment, the phrase "two or more" may have any name that will suit a particular purpose. In one embodiment, "about" or "approximately" may include a deviation of +1% from the indicated term, or in some embodiments a deviation of -1%, or in some embodiments a deviation of ±2.5%, or in some embodiments a deviation of ±5%, or in some embodiments a deviation of ±7.5%, or in some embodiments a deviation of ±10%, or in some embodiments a deviation of ±15%, or in some embodiments a deviation of ±20%, or in some embodiments a deviation of ±25%.
[0061] As used herein, "room temperature" refers to a temperature range of about 10 degrees Celsius to about 25 degrees Celsius. As used herein, "room temperature" refers to a temperature range of about 5 degrees Celsius to about 50 degrees Celsius. In some embodiments, "room temperature" is about 23 degrees Celsius. In some embodiments, the incubation of the silk is carried out at a temperature in the range between 20 degrees Celsius and 40 degrees Celsius. In some embodiments, the incubation of the silk is carried out between 40 degrees Celsius and 60 degrees Celsius. In some embodiments, the incubation of the silk is carried out at about 40 degrees Celsius. In some embodiments, the incubation of the silk is carried out between 5 degrees Celsius and 60 degrees Celsius.
[0062] In some embodiments, the fibers of the present invention include biological fibers. In some embodiments, the fibers consist of biological fibers. In some embodiments, the fibers of the present invention include synthetic fibers.
[0063] In some embodiments, the time period for incubation of silk fibers is between 0 minutes and 5 minutes. In some embodiments, the incubation of silk fibers is between 0 minutes and 10 minutes. In some embodiments, the incubation of silk fibers is between 0 minutes and 20 minutes. In some embodiments, the incubation of silk fibers is between 0 minutes and 30 minutes. In some embodiments, the incubation of silk fibers is between 0 minutes and 60 minutes. In some embodiments, the incubation of silk fibers is between 10 minutes and 20 minutes. In some embodiments, the incubation of silk fibers is between 20 minutes and 30 minutes. In some embodiments, the incubation of silk fibers is between 30 minutes and 60 minutes. In some embodiments, the incubation of silk fibers is up to 1 hour. In some embodiments, the incubation of silk fibers exceeds 1 hour. In one embodiment, the incubation time is between 0.1 minutes and 60 minutes or between 0.1 minutes and 120 minutes. In some embodiments, the incubation of silk fibers is in the range of 1 hour to 3 hours.
[0064] Figure 5 is a schematic depiction of different degumming treatments and processes. The figure depicts a silkworm cocoon cut into small pieces. Subsequently, four different degumming treatments for removing the sericin layer are shown. The treatments include: Na2CO3 and NaOH (0.1M, 0.5M and 1M). After degumming, the fiber is washed and / or rinsed thoroughly with water and dried at room temperature. In one embodiment, after the incubation stage, the degummed fiber is washed / rinsed in water. In one embodiment, after the incubation stage, the degummed fiber is washed / rinsed in a solution. In some embodiments, the terms "rinsing" and "washing" are used interchangeably. In some embodiments, rinsing / washing can include washing the degummed fiber under a stream of water or otherwise placing the degummed fiber in a container (e.g., a beaker) of water and / or solution. In some embodiments, rinsing includes dialysis. Dialysis can be performed using any solution composition optimized for the desired pH and ionic strength, such as: water, a buffer solution, or a mixture containing a variety of aqueous solvents or organic solvents. Membranes, filter parameters, wash times and frequencies, solution volumes and concentrations are selected to optimize specific analytes. In some embodiments, rinsing / washing the degummed fibers is performed more than once. In some embodiments, the water comprises deionized water, purified water and / or filtered water.
[0065] After the degummed silk fibers are rinsed / washed in water / solution, the degummed fibers can be obtained by drying. In some embodiments, the drying can be carried out under any conditions that maintain the structural integrity of the degummed fibers. In some embodiments, the degummed fibers are dried under the flow of a gas. In one embodiment, the gas is an inert gas, such as nitrogen or argon. In one embodiment, the degummed silk fibers are dried in the presence of a vacuum, in a vacuum chamber, and / or in a drying oven. In other embodiments, the degummed silk fibers are dried under ambient conditions. In some embodiments, Figure 5 The method described in produces individual fibers, fiber mats, fiber bundles and / or more than one fiber. In some embodiments, after drying, the fibers are separated to obtain any desired form. In some embodiments, one or more fibers are selected from the formed dried degummed fiber bundle. In one embodiment, individual fibers are removed from the dried degummed fiber bundle for subsequent processing / analysis. In one embodiment, individual fibers are removed from the dried degummed fiber bundle individually for subsequent processing / analysis. In one embodiment, individual fibers are used individually for further testing, and the test results of the individual fibers are further used for analysis as described herein.
[0066]
[0067] Table 1
[0068] In some embodiments, the silk fibers are incubated in the presence of a hydroxide, such as sodium hydroxide (NaOH). As mentioned herein and in one embodiment, "incubating solution", "incubation solution", "incubation medium", "incubating medium", "medium" or "solution" refers to a liquid containing at least one substance in which the fiber is placed. As known to those skilled in the art, other equivalent terms for incubation medium are also used. In one embodiment, the silk fibers are incubated in a solution comprising any of the following: NaOH, LiOH, KOH, RbOH, CsOH, Ca(OH)2, SR(OH)2, BA(OH)2, or any combination thereof. In some embodiments, the silk fibers are incubated in a solution comprising a hydroxide. In some embodiments, the silk fibers are incubated in a solution comprising a hydroxide and water. In some embodiments, the silk fibers are incubated in a solution consisting of a hydroxide and water. In some embodiments, the silk fibers are incubated in a solution comprising at least one hydroxide and water.
[0069] In some embodiments, the incubation solution further comprises at least one buffer. In one embodiment, the incubation solution further comprises at least one weak acid, weak base and / or salt. In other embodiments, the incubation solution further comprises at least one strong acid and / or strong base.
[0070] In some embodiments, 100% of the sericin layer is removed by the process of the present invention. In some embodiments, about 100% of the sericin layer is removed by the process of the present invention. In some embodiments, the incubation process partially removes the glue layer. In some embodiments, 0% to 50% of the glue layer is removed by the method of the present invention. In some embodiments, 0.001% to 50% of the glue layer is removed by the method of the present invention. In other embodiments, 50% to 100% of the glue layer is removed by the method of the present invention. In some embodiments, as defined herein, "partly" or "in part" refers to partial removal of the glue layer, which includes any amount that is not 100%. In one embodiment, the entire glue layer is removed by the method of the present invention. In one embodiment, 100% of the glue layer is removed by the method of the present invention.
[0071] In some embodiments, the sericin layer or glue layer constitutes 0% to 20% of the cross-sectional area and / or volume of the degummed silk fiber. In some embodiments, the sericin layer or glue layer constitutes 0% to 10% of the cross-sectional area and / or volume of the degummed silk fiber. In some embodiments, the sericin layer or glue layer constitutes 0% to 5% of the cross-sectional area and / or volume of the degummed silk fiber. In some embodiments, the sericin layer or glue layer constitutes 0% to 20% of the material mass of the degummed silk fiber. In some embodiments, the sericin layer or glue layer constitutes 0% to 10% of the material mass of the degummed silk fiber. In some embodiments, the sericin layer or glue layer constitutes 0% to 5% of the material mass of the degummed silk fiber. In some embodiments, the sericin layer or glue layer constitutes 0% of the material mass of the degummed silk fiber. In some embodiments, the sericin layer or glue layer constitutes less than 0.1%, or less than 0.01%, or less than 0.001% of the material mass of the degummed silk fiber.
[0072] like Figure 1A Detailed morphological analysis was performed using scanning electron microscopy (SEM), as shown in Figure 1. The analysis revealed that when the removal was performed by the standard protocol using Na2CO3, a thin layer of sericin remained. In contrast, for all NaOH treatments, the glue component was absent ( Figure 1A-Figure 1D). In addition to the visual observations of sericin removal efficiency, the asymmetry of the shape of the silk fibroin fibers can also be seen. As mentioned above, such asymmetry represents an obstacle to the correct determination of the mechanical properties of silk fibroin fibers. This is because existing methods of data analysis obtained from mechanical measurements generally rely on the approximation of a perfect cylindrical shape of the fiber without any defects. Therefore, such an assumption cannot be applied to biological fibers, including silk fibroin fibers. To address this challenge, the subject matter disclosed herein details a method that enables:
[0073] 1. Distinguish between sericin coating and fibroin core fibers;
[0074] 2. Measure the cross-sectional area of the asymmetric composite fiber and each component separately; and
[0075] 3. Establish fiber volume with high precision.
[0076] As discovered in the present invention, these measured parameters are essential for further calculation of the accurate mechanical properties of asymmetric bio-fibers.
[0077] As used herein, the term "asymmetric" refers to any structure that is not completely symmetrical. In some embodiments, "asymmetric" refers to any structure that is partially non-uniform or completely non-uniform. In some embodiments, "asymmetric" refers to a structure that contains defects. In some embodiments, the term "asymmetric" can be used interchangeably with the terms "non-uniform", "ununiform", "uneven" and / or "irregular", without limiting the scope of the present invention.
[0078] In one embodiment, the initial length and final length of the silk fiber that experiences degumming are the same. That is, the initial fiber will not be broken into smaller parts. In some embodiments, there is partial fragmentation of the original silk fiber that experiences degumming. In other embodiments, the initial length and final length of the silk fiber that experiences degumming are different, that is, the silk fiber experiences fragmentation during the degumming process. Ideally, the integrity of the fiber is maintained after experiencing the degumming process, as disclosed in multiple examples herein. In some embodiments, the process is carried out in a solution that does not include alcohol such as ethanol. In some embodiments, the process is carried out in a solution that does not include urea.
[0079] In some embodiments, the incubation solution comprises water and sodium hydroxide. In some embodiments, the incubation solution consists of water and sodium hydroxide.
[0080] In some embodiments, the efficiency of producing degummed fibers is between 50%-100%. In some embodiments, the efficiency of producing degummed fibers is between 60%-80%. In some embodiments, the efficiency of producing degummed fibers is between 80%-100%. In some embodiments, the efficiency of producing degummed fibers is between 90%-100%. In some embodiments, the efficiency of producing degummed fibers is between 95%-100%. In this regard, efficiency refers to the percentage amount of successfully degummed fibers, such as the percentage of completely degummed fibers. Or alternatively, efficiency refers to the percentage of individual fibers that are degummed, for example, all degummed fibers are degummed by a certain percentage. In some embodiments, degumming efficiency can refer to both.
[0081] In some embodiments, the process described herein requires an incubation step to carry out degumming. In addition, it is referred to as a "single" incubation step in this article. A single incubation step refers to placing the silk fiber in an incubation solution only once for the purpose of degumming. As disclosed elsewhere herein, this degumming can refer to complete degumming or partial degumming. After the single-step incubation step, other processes are carried out to obtain the final product.
[0082] Cross-sectional and volumetric analysis of silk fibroin fibers
[0083] Figure 1A A scanning electron microscope image of a silk fiber is depicted. Figure 1B Confocal microscopy imaging of the fibers is depicted. Figure 1C Imaris longitudinal imaging of the fibers is depicted. Figure 1D An Imaris cross section of a fiber is depicted.
[0084] In one embodiment, the staining procedure is combined with confocal microscopy analysis and image processing techniques to measure the cross-section of the fibers and calculate the fiber volume. Figure 1C-Figure 1D ). The intrinsic fluorescence signal in the silk (excitation measured at 346 nm and emission measured at 434 nm) is used to measure the cross-sectional area and volume of asymmetric fibers containing both a fibroin component and a sericin component. In one embodiment, Nile red dye (an environmentally sensitive dye that changes its fluorescence in response to changes in the extinction coefficient of a material) is used for selective staining of only the fibroin component. The Nile red dye emission peak is at about 635 nm.
[0085] like Figure 1DAs shown in Figure 1, for both untreated and Na2CO3 treated fibers, the combination of intrinsic emission from both components of the fiber and emission from the Nile Red dye from only the fibroin component produces an accurate optical distinction between the two components of the fiber (fibroin and sericin). Such distinction aids in calculating the cross section of the fiber and any of its components. As shown herein, such an accurate cross section assessment is extremely important for accurately assessing the mechanical properties of the fiber.
[0086] In some embodiments, other suitable fluorescent dyes may be used for selective dyeing of various components within the fiber.
[0087] In some embodiments, z-stack confocal images are collected for each fiber. These confocal images are further processed into 3D representations ( Figure 1C and Figure 1D ). A "Z-stack" refers to the stacking of two-dimensional images (e.g., cross sections) in any direction to complete a three-dimensional image. Typically, a z-stack will include 2D cross sections along the length of the fiber. A schematic diagram of the z-stacking process is shown in Fig.12 Depicted in.
[0088] In one embodiment, Figure 1D As shown in and as described above, based on the difference between the blue fluorescent signal and the red fluorescent signal, the boundary between the silk fibroin component and the sericin component can be defined.
[0089] The fibroin component and the sericin component are two of a variety of fiber components that can be used in embodiments of the present invention. In some embodiments, the methods of the present invention can be used to distinguish between other fiber components. In some embodiments, the methods of the present invention can distinguish between different forms and structures of the fibroin component and the sericin component themselves. In some embodiments, the fiber comprises biological material. In some embodiments, the fiber comprises non-biological material. In some embodiments, the fiber comprises organic material. In some embodiments, the fiber comprises inorganic material. In one embodiment, the fiber is a natural fiber. In one embodiment, the fiber is a synthetic fiber. In one embodiment, the fiber comprises one component. In one embodiment, the fiber comprises two components. In one embodiment, the fiber comprises three or more components. In one embodiment, each component of the fiber can constitute one part. In one embodiment, each component of the fiber can constitute more than one part. For example and in one embodiment, the fibroin component of an untreated silk fiber constitutes two adjacent fibers, such as, for example Figure 1D All such sections and their specific cross-sections can be evaluated using the novel method of the present invention.
[0090] Due to the asymmetric shape and inhomogeneity of silk fibers, volume parameters are generally not used in the calculation of silk mechanics. In contrast, in the method of the present invention, cross-sectional values are used. In order to infer the cross-sectional parameters of silk fiber components, post-processing analysis has been applied. The original confocal image is converted into a binary format to calculate the cross-sectional area of each component separately and combine. For this purpose and in some embodiments, software that integrates over the entire image to obtain the cross-sectional area of the fiber component is used. Then, the obtained values for the cross-sections of all components are used for mechanical calculations as described in detail below. The cross-sectional analysis shows the inconsistency and large standard deviation (STD) of the fibers processed by the standard Na2CO3 degumming process (see Fig. 6A and Fig. 6F ). In contrast, the novel NaOH 0.5 M treatment obtained the narrowest STD ( Figure 6C and Fig. 6F ). These differences may result from better solubility of the sericin component in NaOH and / or from the absence or reduction of thermal damage in the silk fibroin fibers subjected to this novel treatment process.
[0091] A summary of the synergistic analysis of the measured cross-sectional areas of untreated fibers, fibers degummed via a standard method (Na2CO3) and silk fibers treated with NaOH-based solutions is given in Figure 2A Neutral 6A to 6F Note that Figure 6A-6D In the images, the cross-section of the treated fiber is measured. In these images, the right image is labeled "Silk Fibroin and Sericin" and refers to the treated fiber, wherein the fiber comprises mainly or entirely silk fibroin, and in some embodiments comprises a small portion of sericin. Figure 6A-6D The left and right images in show similar cross-sections because they were taken after treatment, and the sericin portion in these treated fibers is very small or absent. Fig. 6E The right image shows silk fibroin and sericin to which no treatment was applied. Fig. 6E The left image in Figure 2 also measures untreated fibers. A cross section of only silk fibroin in untreated fibers was obtained, as shown in Figure 2. Figure 1D As shown in Figure 1 (upper right). As detailed herein, selective Nile Red staining allows the differentiation of fibroin and sericin in this image. Analysis showed that there was a substantial difference in the effectiveness of sericin removal when comparing the standard method and the newly developed NaOH-based process (see FIG. 6B to FIG. 6D). Although small amounts of sericin components have been detected for standard protocols, such as Na2CO3, fiber degumming using NaOH did not show the presence of any glue. At high NaOH molar concentrations (e.g., about 1 M), microscale bundles disintegrated into individual nanofibrils (see FIG. 7A to FIG. 7D , showing multiple regions along the fiber). In addition, Figure 2A and Figure 6C Analysis of the measured cross-sectional areas shown in revealed that degumming performed in NaOH (0.5 M) resulted in the smallest standard deviation (STD) values, with almost complete overlap between the values obtained from confocal microscopy analysis.
[0092] Cross-sectional area measurements of silk fibroin and silk fibroin and sericin are performed before or after treatment as desired. In one embodiment, a (fibroin + sericin) cross section is taken before treatment, and for the fiber after treatment, only the cross section of the silk fibroin is measured. In some embodiments, after treatment, the sericin layer is removed and only the cross section of the silk fibroin is measured. In one embodiment, silk fibroin and (fibroin + sericin) cross sections are taken from an image of a stained fiber before treatment, where the silk fibroin and sericin have different colors (see details below). In one embodiment, for example, in the case where some sericin is left on the fiber after treatment, measurements of silk fibroin and residual sericin (fibroin and sericin) are performed after treatment.
[0093] Figure 2A Represents the cross-sectional areas calculated based on images obtained from confocal analysis and further processing. Figure 2B Shown are stress-strain curves of untreated silk fiber and degummed silk fiber. Figure 2C It is a summary from Figure 2A Graph of the true breaking strain of untreated silk fiber and degummed silk fiber. Figure 2D Indicates the summary from Figure 2A Graph of Young's modulus of untreated silk fiber and degummed silk fiber. Figure 2E It is a summary from Figure 2A Graph of the calculated (true) tensile strength of untreated silk fibers and degummed silk fibers. Figure 2F is a graphical representation of the calculated two-parameter Weibull distribution plot of fiber strength.
[0094] Method of the present invention
[0095] In one embodiment, the present invention provides a method for removing at least a portion of a glue layer from a silk fiber, the method comprising: incubating the silk fiber in an incubation medium, the incubation medium comprising a hydroxide. In some embodiments, the incubation medium consists of a hydroxide and water.
[0096] In one embodiment, the method is carried out at a temperature in the range of 5 degrees Celsius to 60 degrees Celsius (°C). In one embodiment, the hydroxide is selected from: NaOH, LiOH, KOH, RbOH, CsOH, Ca(OH)2, Sr(OH)2 or Ba(OH)2 or a combination thereof. In one embodiment, the source of the hydroxide in the incubation medium is: NaOH, LiOH, KOH, RbOH, CsOH, Ca(OH)2, Sr(OH)2, Ba(OH)2 or a combination thereof. In one embodiment, the concentration of the hydroxide in the incubation medium is in the range of about 0.1M to 1M. In one embodiment, the concentration of the hydroxide in the incubation medium is in the range of about 0.05M to 0.8M. In one embodiment, the concentration of the hydroxide in the incubation medium is in the range of about 0.4M to 0.8M. In one embodiment, a single incubation step is performed for degumming, wherein the incubation medium consists of one hydroxide and water. In one embodiment, a single incubation step is performed for degumming, wherein the incubation medium comprises at least one hydroxide and water.
[0097] In one embodiment, the incubation medium is a solution comprising a hydroxide. In one embodiment, the solution is an aqueous solution. In one embodiment, the solution comprises water and a base. In one embodiment, the base comprises a hydroxide. In one embodiment, the base is a strong base. In one embodiment, the incubation medium comprises water, hydroxide anions, and metal cations. In some embodiments, the hydroxide is referred to as (OH) - . In some embodiments, for simplicity, the ionic material (e.g., NaOH) that is a source of hydroxide is referred to as hydroxide. In one embodiment, the incubation medium further comprises at least one buffer. In one embodiment, the incubation medium further comprises at least one salt. In one embodiment, the incubation is carried out between 1 minute and 60 minutes. In one embodiment, the incubation is carried out between 5 minutes and 40 minutes. In one embodiment, the incubation is carried out for more than 5 minutes. In one embodiment, the method further comprises rinsing the silk fibers in a liquid after incubation. In one embodiment, the rinse liquid is water. In one embodiment, the rinse liquid comprises water or a solution. In one embodiment, the rinsing comprises dialysis. In one embodiment, the method further comprises drying the silk fibers after rinsing with the liquid. In one embodiment, the method further comprises separating the silk fibers into separate fibers. In one embodiment, the method further comprises selecting a single fiber from a fiber bundle.
[0098] Methods for determining true mechanical properties
[0099] In order to determine the true mechanical properties of silk fibers, the following general steps need to be performed. It should be noted that many silk fibers include asymmetric structures, and many silk fibers contain defects (such as fractures at the surface). Despite the non-uniform nature of the fiber, the present invention helps to determine the cross-sectional area. In principle, this type of calculation can be extended to any fiber, even non-biological fibers, as explained herein. Establishing accurate measurements of cross-sectional area is crucial for determining mechanical properties and characteristics.
[0100] Samples to be imaged are usually prepared in a confocal microscope. Therefore, silk fibers can be dyed to enhance detection in microscopes such as confocal microscopes. Then, cross-sectional images are collected along the length of the fiber using a confocal microscope. Imaging parameters are usually optimized to ensure the high contrast of the cross section at different focal planes. Imaging parameters such as laser power, wavelength, gain, exposure time and focus are selected to optimize image quality. Usually, considering the structure of the silk fiber, the image is optimized to make multiple regions in the cross section easily distinguishable. A pile of images are sorted and image processing is performed using software. In different embodiments, the z-axis (i.e., the axis along the length of the fiber) increment is selected to optimize image processing. In some embodiments, the z increment is small, and the total cross-sectional area is integrated along the length of the silk fiber. Ideally, these increments are very small. The software measures the cross-sectional area of each image, and the cross-sectional area is integrated along the entire length of the silk fiber to obtain volume.
[0101] In one embodiment, the present invention provides a method for determining the average mechanical properties of more than one asymmetric fiber, the method comprising:
[0102] a) obtaining more than one cross-sectional image along the length of one of the asymmetric fibers using a confocal microscope;
[0103] b) Calculate the cross-sectional area of the asymmetric fiber;
[0104] c) calculating the average cross-sectional area along the length of the asymmetric fiber;
[0105] d) measuring the extension of the asymmetric fiber relative to the load until the asymmetric fiber breaks;
[0106] e) using the average cross-sectional area to obtain stress-strain diagrams for asymmetric fibers;
[0107] f) Obtaining the maximum strength and Young's modulus from the stress-strain diagram of the asymmetric fiber;
[0108] g) performing stage 'a' to stage 'f' on more than one asymmetric fiber to obtain more than one stress / strain data set;
[0109] h) Calculate the average maximum strength and average Young's modulus of more than one asymmetric fiber.
[0110] In one embodiment, the true stress (σ t ) and true strain (ε t ) calculates the stress-strain diagram using the following equation:
[0111]
[0112] In turn, the true stress and true strain are also used to determine the true Young's modulus.
[0113] The Weibull parameter is a statistical parameter used to characterize the strength, failure and reliability of materials such as silk fibers. It provides a statistical distribution of fiber strength within a collection of such fibers. In one embodiment, the method also includes utilizing a two-parameter Weibull distribution, wherein the method includes:
[0114] a) rank the maximum intensity of more than one stress / strain data set from lowest to highest and assign a number to the data set;
[0115] b) calculating the natural logarithm of the maximum intensity of each data set;
[0116] c) Calculate the failure probability f(σ) of each data set;
[0117] d) Plot the natural logarithm of the maximum intensity versus ln(-ln(1-f(σ));
[0118] e) From the graph of 'd', the shape parameter β is extracted from the gradient and the scale parameter α is extracted from α = exp(intercept / β).
[0119] In one embodiment, shape parameter β and scale parameter α provide a measure of the mechanical properties of the fiber. In one embodiment, the value of shape parameter β and scale parameter α gives an indication of the strength of the fiber material, which is valuable information for users of the material. In one embodiment, in view of the multiple applications of the fiber or its components, the Weibull parameters provide important information for users of the fiber. In one embodiment, the novel cross-sectional evaluation technology proposed herein enables easy and accurate calculation of the Weibull parameters. In one embodiment, this accurate calculation of the Weibull parameters achieved by the method of the present invention provides a basic evaluation of the mechanical properties of the fiber. In some embodiments, such an evaluation is crucial in order to determine whether the fiber is suitable for a particular application.
[0120] In one embodiment, the asymmetric fibers are stained with a dye prior to step (a) of: a) obtaining more than one cross-sectional image along the length of one of the asymmetric fibers using a confocal microscope.
[0121] In one embodiment, the asymmetric fibers are of bio-origin. In one embodiment, the asymmetric fibers are degummed. In one embodiment, the asymmetric fibers are coated with an additional material. In one embodiment, the asymmetric fibers are not degummed.
[0122] In one embodiment, the fiber is of biological origin. In one embodiment, the fiber is a natural fiber. In one embodiment, the fiber is synthetic. In one embodiment, the fiber is organic. In one embodiment, the fiber is inorganic. In one embodiment, the fiber is a polymer. In one embodiment, the fiber comprises organic and inorganic materials. In one embodiment, the fiber comprises silicone. In one embodiment, the fiber comprises metal ions. In one embodiment, the fiber is derived from spiders. In one embodiment, the fiber is derived from any of the following: Hymenoptera (bees, wasps and ants), silverfish, mayflies, thrips, leafhoppers, beetles, lacewings, fleas, flies, midges, arthropods, arachnids and spiders. In one embodiment, the fiber is derived from mammals. In some embodiments, the fiber comprises hair or fur.
[0123] The fiber of the present invention
[0124] In one embodiment, the present invention provides a degummed silk fiber, the degummed silk fiber comprising a core and a glue layer, wherein the glue layer constitutes 0% to 20% of the cross-sectional area of the degummed silk fiber. In one embodiment, the degummed silk fiber does not contain any glue layer. In one embodiment, the fiber contains a negligible amount of glue layer. In one embodiment, the glue layer constitutes less than 1% of the cross-sectional area of the degummed silk fiber. In one embodiment, the glue layer constitutes less than 0.01%, or less than 0.1%, or less than 0.5%, or less than 5%, or less than 10% of the cross-sectional area of the degummed silk fiber.
[0125] In one embodiment, the present invention provides a degummed silk fiber, the degummed silk fiber comprises a core and a glue layer, wherein the glue layer constitutes 0wt% to 20wt% of the degummed silk fiber. In one embodiment, the glue layer constitutes less than 1wt% of the degummed silk fiber. In one embodiment, the glue layer constitutes less than 0.01wt%, or less than 0.1wt%, or less than 0.5wt%, or less than 5wt%, or less than 10wt% of the degummed silk fiber. In some embodiments, the removal of the glue layer can be complete, or in other embodiments is incomplete.
[0126] In one embodiment, the degummed silk fiber exhibits a Young's modulus of at least 10 GPa. In one embodiment, the degummed silk fiber exhibits a Young's modulus of at least 10 GPa. In one embodiment, the degummed silk fiber exhibits a Young's modulus between 5 GPa-15 GPa. In one embodiment, the degummed silk fiber exhibits a Young's modulus that is at least 1.5 times larger than the Young's modulus of the untreated silk fiber. In one embodiment, the degummed silk fiber exhibits a Young's modulus that is at least 2 times larger than the Young's modulus of the untreated silk fiber. In some embodiments, the terms "Young's modulus" and "true Young's modulus" are used interchangeably.
[0127] In one embodiment, the degummed silk fiber exhibits a tensile strength of at least 400 MPa. In one embodiment, the degummed silk fiber exhibits a tensile strength of 400 MPa. In one embodiment, the degummed silk fiber exhibits a tensile strength of at least 300 MPa. In one embodiment, the degummed silk fiber exhibits a tensile strength of at least 500 MPa. In one embodiment, the degummed silk fiber exhibits a tensile strength of at least 550 MPa. In some embodiments, the terms "tensile strength" and "true tensile strength" are used interchangeably.
[0128] In one embodiment, the degummed silk fibers exhibit a strain at break of at least 0.2. In some embodiments, the terms "strain at break" and "true strain at break" are used interchangeably. In one embodiment, the degummed silk fibers exhibit a strain at break of at least 0.3. In one embodiment, the degummed silk fibers exhibit a Weibull characteristic strength parameter (α) of at least 400 MPa.
[0129] In one embodiment, the degummed silk fibers exhibit a Weibull characteristic intensity parameter (α) that is at least 1.2 times greater than the parameter for untreated silk fibers. In one embodiment, the degummed silk fibers exhibit a Weibull shape parameter (β) of at least 4. In one embodiment, the degummed silk fibers are produced by a method as described above.
[0130] In one embodiment, the length of the fiber is in the micrometer range. In one embodiment, the length of the fiber is in the centimeter range. In one embodiment, the length of the fiber is in the range between 1 μm and 10 cm. In one embodiment, the length of the fiber is in the range between 1 mm and 10 cm. In one embodiment, the length of the fiber is in the range between 1 mm and 4 cm. In one embodiment, the fiber includes nanofibers. In one embodiment, the thickness of the fiber is in the range between 1 μm and 50 μm. In one embodiment, for asymmetric fibers, the thickness can have different values in different directions measured along the cross-sectional area of the fiber. In one embodiment, such a variable thickness value is in the range between 1 μm and 50 μm. Fibers with a thickness less than 1 μm or greater than 50 μm are also included in embodiments of the present invention. In some embodiments, the method of the present invention as described herein is applicable to fibers with a thickness less than 1 μm or greater than 50 μm. In some embodiments, the method of the present invention as described herein is applicable to fibers with a thickness value in the range between 1 μm and 50 μm. In one embodiment, the degumming method of the present invention is applicable to coated fibers of any thickness. In one embodiment, the method of evaluating the average cross-section of a fiber as described herein is applicable to any fiber having a thickness that can be measured using a microscope. In one embodiment, the method further comprises spinning the degummed silk fiber into yarn or weaving into a mat or fabric.
[0131] Reconstructed silk fibroin material of the present invention
[0132] In one embodiment, the present invention provides a reconstructed silk fibroin (RSF) material in the form of a solution, the material comprising:
[0133] fibroin soluble protein derived from degummed silk fibers as described above; and
[0134] ·liquid.
[0135] In one embodiment, the liquid is water. In one embodiment, the liquid comprises water. In one embodiment, the reconstructed silk fibroin material comprises small protein molecules. In one embodiment, the liquid further comprises any one selected from the group consisting of a buffer, a salt, a detergent, and a reducing agent, or any combination thereof.
[0136] definition
[0137] As used herein, "glue layer" refers to a layer that coats a silk fiber. In one embodiment, the coating comprises sericin. In one embodiment, the coating is asymmetric. In one embodiment, the glue layer coats only a portion of the fiber. In one embodiment, the glue layer surrounds at least one fibroin core. In one embodiment, a silk fiber comprises two fibroin segments, such as Figure 1D In one embodiment, the silk fiber comprises at least one fibroin core coated with sericin. In one embodiment, the glue coats each of the two fibroin segments. In one embodiment, the glue surrounds each of the two fibroin segments. In one embodiment, the glue surrounds two fibroin segments. In one embodiment, there is only one fibroin segment and the glue surrounds the one fibroin segment. In one embodiment, the glue is present between the two fibroin segments. In one embodiment, the glue surrounds one or more fibroin segments (fibroin segment(s)) and is also present between the two fibroin segments. In one embodiment, the glue coats only a portion of certain cross-sectional areas of the fibroin segments. In one embodiment, the extent of the glue coating varies along the length of the fiber.
[0138] As used herein, "reconstructed" refers to a solution comprising the components of the degummed fiber. In one embodiment, "reconstructed" refers to a solution comprising the components of the fiber. In some embodiments, the reconstructed silk fibroin refers to a liquid comprising separate silk fibroin and water. In one embodiment, the reconstructed silk fibroin is in the form of a suspension. In one embodiment, the solution is transparent. In one embodiment, the protein in the solution is completely soluble.
[0139] As referred to herein, "incubating medium," "incubation medium," "incubation solution," "incubating solution," "medium" or "solution" refers to a liquid containing at least one substance into which the fibers or components thereof are placed.
[0140] In one embodiment, as referred to herein, "hydroxide" is a diatomic anion having the chemical formula OH-, comprising an oxygen atom and a hydrogen atom held together by a single covalent bond.
[0141] As used herein, the term "asymmetric" refers to any structure that is not completely symmetrical. In some embodiments, "asymmetric" refers to any structure that is partially non-uniform or completely non-uniform. In some embodiments, "asymmetric" refers to a structure that contains defects. In some embodiments, the term "asymmetric" can be used interchangeably with the terms "non-uniform", "ununiform", "uneven" and / or "irregular", without limiting the scope of the present invention.
[0142] As used herein, the term "load" refers to the force applied in a tensile test, measured in Newtons. As used herein, the term "extension" refers to the amount of increase in the length of an object, measured in meters. As used herein, the terms "tensile strength," "maximum strength," and "strength" are interchangeable. Tensile strength is the maximum stress that a material can withstand when stretched or pulled before breaking. In some embodiments, tensile strength is measured in Pascals, Pa, or Megapascals, MPa.
[0143] As used herein, "stress" (Pa) is a physical quantity representing the internal force that adjacent particles of a continuous material exert on each other, while "strain" (dimensionless) is a measure of the deformation of a material. In some embodiments, stress is calculated as force divided by the cross-sectional area of the material under load. In some embodiments, "strain" represents the displacement between particles in vivo relative to a reference length.
[0144] As used herein, the term "Young's modulus" (Pa or GPa) refers to a mechanical property that measures the tensile or compressive stiffness of a solid material when a force is applied longitudinally. In some embodiments, it is defined as stress divided by strain.
[0145] As used herein, the "shape parameter" β (dimensionless) is a parameter extracted from the Weibull distribution analysis, which depends on the defect size and is a measure of strength variability (higher β values mean lower strength variability) and therefore also a measure of fiber reliability.
[0146] As used herein, "scale parameter" a (MPa) is the scale parameter of the Weibull distribution, which represents the average or characteristic strength of the fiber according to a distribution that depends on the stress configuration and the test specimen size.
[0147] As described herein, σ refers to stress. More specifically, σ tσ refers to 'true stress' as described herein. In some embodiments, any reference to stress refers to true stress. In some embodiments, σ represents strength - how strong a material is under applied stress. In some embodiments, the strength σ is taken from a stress-strain diagram, where stress is also represented by σ. Thus, in embodiments of the present invention, σ represents stress and strength, as is apparent from the relevant context in certain embodiments and as known in the art. Similarly, as described herein, ε refers to strain. More specifically, ε t refers to 'true strain' as described herein. In some embodiments, any reference to strain refers to true strain. Example
[0148] Example 1
[0149] Mechanical properties and thermal stability of silk fibroin fibers
[0150] Multiple repeated tensile tests were performed on single fibers to measure the effects of different degumming methods on the mechanical properties of Bombyx mori silk fibers.
[0151] FIG. 2B to FIG. 2F Table 2 shows the Young's modulus (E), tensile strength (σ t ) and fracture strain (ε t ). The calculation of the mechanical data parameters is based on the measured cross-sectional area of the fiber before and after the degumming process, as shown in Figure 8. FIG. 2B to FIG. 2F The measured and calculated mechanical properties summarized in Table 2 show the effect of different degumming treatments on the structural behavior of silk fibers. In addition, it serves as a comparison with previous studies in which silk fibers were inaccurately considered to have a perfect circular or elliptical cross-sectional shape.
[0152] The tensile stress-strain curves show an initial and concise elastic response (~1%-1.5% strain) for all fibers, followed by a longer plastic behavior ( Figure 2B and Figure 8). The high scatter of the obtained curves (see Figure 8) is characteristic of imperfect biomaterials with low symmetry and the presence of defects. After yielding to the applied stress, the fibers exhibit strain hardening behavior followed by strain weakening behavior and fluctuations in stress as they gradually fail.
[0153] Table 2 is a summary of the tensile data (mean ± SD) of the measurements of untreated silk fibers and for silk fibers degummed using standard methods such as Na2CO3 treatment methods. The tensile data of the measurements of the treatment methods developed herein are further summarized in the table. In some embodiments, the terms "tensile strength", "maximum strength" and "strength" are interchangeable. Tensile strength is the maximum stress that a material can withstand when stretched or pulled before breaking.
[0154] The several studies on the tensile properties of silk fibers are usually presented in terms of engineering quantities, representing only a practical approximation of the true stress values and true strain values experienced by the silk fibers, rather than a complete analysis of the mechanical properties of the material. This is partly because direct measurements of the instantaneous cross-sectional area are difficult to obtain, or because the validity of the assumption of a constant volume of the fiber is not taken into account in the experimental measurements. The mechanical properties of silk fibers are strongly affected by which set of tensile parameters is chosen (real parameters or engineering parameters), since engineering values may lead to misinterpretation of experiments combining results from different strain ranges. The initial real cross-sectional area of the fiber ( Figure 2A ) into mechanical calculations is crucial to obtain an accurate understanding of the mechanical properties of these fibers, since the initial cross-sectional area has a direct influence on the tensile stress according to the relationship σ = F / A0, where σ is the stress, F is the applied force and A0 is the initial cross-sectional area of the fiber. Determination of the "true" stress and true strain values of the fiber: The engineering or "nominal" stress and strain values, denoted here as σ, are obtained from the measured load (P) and displacement (δ) values according to the following relationships: e and ε e : and Where A0 is the initial cross-sectional area of the sample and is considered constant throughout the test, and l0 is the initial length of the sample, equivalent to the gauge length of the specimen in a tensile test. e ) is plotted as strain (ε e ) as a function of . This curve should be interpreted with caution, especially above the elastic limit, because the sample dimensions undergo substantial changes from their initial values. To elucidate a more accurate mechanical behavior of the fiber under tensile stress, the true stress (σ t ) and true strain (ε t ). The mathematical calculation of true stress and true strain is possible under the assumption of volume uniformity during stretching. This assumption is valid in the elastic region of the curve because any change in volume in this region will be very small. Similarly, this assumption is valid in the plastic region because materials such as silk fibers are considered to be incompressible during plastic deformation. In addition, the true stress (σ t) and true strain (ε t ) can be mathematically defined as:
[0155]
[0156] Where A is the cross-sectional area of the sample, dε is the increment of strain, dl is the increment of length, and l is the length of the fiber. Considering that the volume of the sample remains constant.
[0157] In addition, considering the significant plastic deformation events of silk and the mechanical phenomena observed in such a state, such as strain hardening, determining the true stress and true strain of silk fibers is of great significance for understanding the actual mechanical properties of the material. This paper discusses the rationality and calculation of the true stress and true strain values of fibers and their differences from the "nominal" or engineering stress-strain.
[0158] Table 2 shows a summary of the measured tensile data (mean ± SD) for untreated silk fibers and silk fibers degummed by using the standard method as well as the developed treatment method.
[0159] Table 2
[0160]
[0161] The true tensile stress-strain curves calculated using equations (5) and (6) show an initial and concise elastic response (~1%-1.5% strain) for all fibers, followed by a longer plastic behavior (Figure 8). The high scatter of the obtained curves (Figure 8) is characteristic of imperfect biomaterials with low symmetry and defects. After yielding to the applied stress, the fibers reveal strain hardening properties and fluctuations in stress as they gradually fail.
[0162] This is attributed to the opening, rearrangement, and gradual breaking of the β-sheets in the silk fibroin fibers during deformation along the fiber axis. In addition, strain hardening has the purpose of resisting failure and increasing the mechanical strength of the fiber, as seen in other biomaterials with similar capabilities.
[0163] Similar strain hardening / weakening behavior has been previously observed in spider silk and A. pernyi silk. Furthermore, strain hardening has the purpose of resisting failure and increasing the mechanical strength of the fiber, as seen in other biomaterials with similar capabilities.
[0164] In a simple model, an untreated silk fiber of Bombyx mori contains two fibroin fibers encapsulated in a sericin shell, as discussed above and shown in FIG. 1 (see the figure "Untreated Silk Fibers" above). The mechanical response of each fibroin fiber was observed in the tensile test and Fig. 8AIndicated by arrows in the figure. As the strain propagates throughout the stretch, the stress applied to the fiber gradually increases; when the first silk fibroin fiber breaks, it is noted that the stress drops by about half of its original magnitude. This is followed by a continued increase in strain until the catastrophic break of the second silk fibroin fiber is complete. The ability of adjacent silk fibroin fibers in a single silk fiber to independently resist different strains can have a positive impact on the toughness of the entire fiber. After the first fiber breaks, the second fiber can still absorb more energy through longer plastic deformation. In the case of all treated fibers, it was observed that the random drop in stress was effectively recovered.
[0165] The elastic modulus, strength and breaking strain of silkworm obtained from the measurements are shown ( FIG. 2C to FIG. 2E ).
[0166] Surface treatment of silkworm fibers resulted in increased E values ( Figure 2D ), because after degumming, only single silk fibroin fibers without the soft sericin shell were tested.
[0167] The results of degumming of silkworm silk using NaOH 0.1M and NaOH 0.5M were as follows: Figure 2E and the highest σ values of ~420 MPa and ~480 MPa, respectively, shown in Table 2. These values are 16%-33% higher than those obtained by standard degumming treatment with Na2CO3 (~360 MPa). The results show that after degumming silk using the standard protocol (i.e. boiling in a solution containing Na2CO3), a higher number of defects are generated at the fiber surface, affecting the overall strength of the material. In general, although not absolutely, sericin does not contribute to the strength of the silk. In general, as shown herein, degumming of Bombyx mori silk with NaOH 0.5M results in higher strength than degummed silk from A. mylitta, Antheraea pernyi, Scricini, with improvements ranging from 2% to 70%.
[0168] The strength of the fiber is affected by both defects and non-uniform cross-sectional area along the fiber. To further understand and correlate the effect of the debonding process on fiber strength, the present invention utilizes a two-parameter Weibull distribution. The theory and rationale for using this distribution are discussed below. First, the data is sorted and a failure probability is assigned to each data point (of strength) and then plotted using equation (3) as shown below, yielding Figure 2F Note that Figure 2F The "f" and "σf" in the X / Y labels of represent the probability of failure of the fiber under the applied stress (σ). In Equations 1-4 below, f(σ) represents this value. Equation 1:
[0169]
[0170] After equation expansion as shown below, Equation 3 is obtained:
[0171] ln[-ln(1-f(σ))]=βlnσ-βlnα (3)
[0172] The left half of the equation is Figure 2F The right half of this equation represents a linear graph where β is the slope, lnσ is 'X' and -βlnα is the intercept. Figure 2F The X-axis of see ln(σf).
[0173] Figure 2F The slope in indicates the intensity distribution width. Figure 2F The creep in the curve usually appears in a small sample population. The data show that the silk degummed with NaOH 0.5M exhibits a larger β value (the intercept is not in Figure 2F ), which is a shape parameter indicating lower intensity variability compared to the Na2CO3 and NaOH 0.1M degumming treatments, which show a broader intensity distribution through their lower β values (Table 2). The characteristic intensity or scale parameter (α) shown for each sample in Table 2 specifies the intensity distribution along Figure 2F The distribution position of the x-axis.
[0174] Treatment with 1 M NaOH produced fibers with lower E and σ values (respectively FIG. 2D to FIG. 2E and Table 2). This may be the result of a more severe degumming treatment, which may have damaged the surface and structural integrity of the silk fibroin fibers ( Figure 2F Large deformations (similar in some embodiments to those found when boiling the fibers) were also observed after this aggressive degumming process. The crystalline phase (in this case, β-sheets) imparts dimensional stability to the silk fibroin fibers, which, in some interpretations, may be lost due to degradation of this phase during the harsh degumming process.
[0175] The breaking strain of silk fibroin after degumming silk with NaOH 0.1M and NaOH 0.5M, respectively, is reduced compared to the breaking strain of silk in its native form (Table 2). It has been shown previously that stretching the microstructure results in molecular orientation of the β-sheets, resulting in a higher degree of fiber microstructure crystallinity, and thus improved mechanical strength and reduced strain. Treatment of the fibers with 0.1M and 0.5M NaOH is a less harsh degumming process than the standard protocol (Na2CO3). FIG. 2 shows only representative examples, and therefore deviates slightly from the average values in Table 2.
[0176] The difference in degumming treatment, especially the use of standard Na2CO3 scheme compared to NaOH-based degumming without thermal damage, leads to changes in the thermal stability of the fibers. In one example, fibers with a higher degree of molecular orientation and a higher degree of crystallinity tend to show higher thermal stability. To this end, thermogravimetric analysis (TGA) was performed, the results of which are summarized in Figure 3. Figure 3A and Figure 3B Five replicates of TGA scans of degummed silk fibroin fibers in the presence of Na2CO3 and NaOH 0.5M, respectively, are shown. Figure 3C is a graph showing the onset of TGA. Figure 3D Represents the first derivative of the TGA curve of the fiber degummed with NaOH. The present analysis shows three main peaks of weight loss detected for the untreated fiber and for the fibers subjected to different degumming treatments: the first peak varies between 40°C-50°C (weight loss 6%-8%), related to the moisture loss; the second peak is between 270°C-300°C, related to the slow thermal decomposition stage (weight loss 40%-45%); and the weight loss at the third stage is recorded between 300°C-350°C (weight loss 19%-22%), which is mainly caused by the cleavage of peptide bonds and side groups. Although only small differences have been detected in the thermal stability of degummed silk fibers by using the standard protocol and the NaOH-based treatment (see Figures 3 and 9 and Table 3), the main difference lies in the reproducibility of the measurements. Therefore, for the standard protocol, a large variation in the weight loss temperature (at the second peak between 270°C-300°C) has been recorded (STD ± 5.53°C), which may originate from the large number of defects or low crystallinity caused by the standard high temperature heat treatment. TGA data recorded from samples degummed in the presence of NaOH were highly reproducible with a STD of ± 1.94°C. In some experiments, large variations in weight loss temperature were recorded with a STD of < 2.6%. In other experiments, TGA data recorded from samples degummed in the presence of NaOH were reproducible with a STD of < 6%.
[0177]
[0178] Table 3: Analysis of weight loss based on the results obtained from TGA measurements.
[0179] Example 2
[0180] Structural characteristics and mechanism of silk fiber degumming
[0181] In order to further understand the structural source of the mechanical strength of the increase of the silk fiber processed by NaOH compared with the standard treatment, X-ray analysis was performed to detect the difference of the crystallization fraction of the treated fiber. In addition, gel electrophoresis was performed to check the integrity of the protein molecule. Generally, the silk fibroin constituting the silk fibroin fiber exists in a crystalline form or an amorphous (random coil) form. The fine balance between these two forms (most of the crystalline components are decorated with a small portion of disordered regions) defines the special mechanical properties of the fiber. XRD analysis shows that 2θ has characteristic diffraction peaks at 9.5 °, 20.7 °, 24.3 ° and 39.7 ° (corresponding crystal spacing is and like Figure 4B The β-sheet crystal structure of silk II is indicated by the diffraction peaks at 12.2°, 19.7°, and 24.7° (corresponding to the crystal spacing of and ) indicates the structure of silk I which is a disordered random coil silk protein. and The diffraction peak of is not present in the Na2CO3 treated sample, indicating a decrease in both the crystalline fraction and the disordered fraction of the protein. Such an event may result from the loss / disintegration of protein subunits. Silk fibroin is a large globular protein (~400kDa-450 kDa) containing two protein subunits of a heavy chain and a light chain, which are connected via a single disulfide bridge.
[0182] Therefore, in order to further examine the changes in the integrity of the silk fibroin molecules with the applied treatments, electrophoretic protein gel analysis has been performed. In detail, denaturing gels have been used to test the presence of heavy and light chain protein subunits. β-mercaptoethanol (a chemical component used in electrophoretic gel analysis) is able to destroy disulfide (SS) bridges via a reduction reaction, denaturing the protein and thus providing additional information about the protein chains. Figure 4A The results summarized in reveal that light chain subunits were absent in samples degummed using the standard Na2CO3-based protocol, whereas for NaOH-treated samples, the presence of both heavy and light chain protein subunits has been observed. This points to the effectiveness of the NaOH-based degumming method for gentle removal of the gum components without causing damage to the protein units.
[0183] Figure 4A The figure shows the gel electrophoresis analysis of silk fibroin molecules. Figure 4B The figure shows the XRD analysis performed on the degummed fibers and compared with untreated silk fibroin fibers. Seven major 2θ peaks were recorded, namely 10°, 13°, 18°, 20.7°, 25° and 29°. Figure 4Cis a rheological analysis of the change in viscosity in response to applied shear, where the shear rate ranges from 0.1 s -1 Increase to 500s -1 and from 500s -1 Back to 0.1s -1 The following samples were analyzed: native silk fibroin solution obtained from silkworm glands via dissection, RSF solution obtained via chemical redissolution of degummed silk fibers in the presence of Na2CO3, NaOH 0.1 M, NaOH 0.5 M and NaOH 1 M. The shaded colors represent standard deviations.
[0184] Example 3
[0185] Rheology and structural hierarchy of reconstructed silk fibroin from degummed silk fibroin fibers
[0186] To illustrate the effect of different degumming procedures on the rheological behavior of reconstructed silk fibroin (RSF) fluids, the viscosity change in response to applied shear was measured, where the shear rate was increased from 0.1 s -1 Increase to 500s -1 and from 500s -1 Reduced back to 0.1s -1 In addition, a comparison was made between the rheological properties of RSF obtained via different degumming protocols followed by chemical re-dissolution and native silk fibroin (NSF) extracted directly from the silk gland of Bombyx mori via dissection. The viscosity values recorded for RSF solutions (obtained following a protocol including degumming steps in the presence of 0.5 M NaOH and 1 M NaOH) were significantly higher than those obtained via the standard degumming protocol ( Figure 4C ). Such values are comparable to those of natural silk. At the maximum shear rate (500s -1 ), the viscosities of the silk solutions reconstituted from fibers degummed with 0.5 M NaOH and 1 M NaOH were 0.03 Pa.s and 0.05 Pa.s, respectively. However, the viscosity of the solution reconstituted from fibers degummed with 0.1 M NaOH was 0.03 Pa.s and 0.05 Pa.s, respectively. -1 The shear rate is 0.25Pa.s. At the minimum shear rate (0.1s -1 ), the viscosity of the RSF solutions (degumming step 0.5M NaOH and 1M NaOH) were 501.17 Pa.s and 644.53 Pa.s, respectively. For 0.1M NaOH, the viscosity was 374 Pa.s. In contrast, the RSF from the degummed fiber using NaOH 0.1M had a higher viscosity than Na2CO3, but not significantly. This observation can be explained by the insufficient NaOH concentration to effectively remove the glue layer, which further affects the quality of the RSF solution, similar to Na2CO3.
[0187] Example 4
[0188] Calculate the statistical distribution of fiber strength
[0189] When stress is applied to a rigid material, stress concentrations occur at localized areas due to variations in sample geometry, cracks and surface irregularities, among other things. All of these manifestations of stress concentration are observed in silkworm fibers, where the geometry of the fiber is constantly changing, such as that formed by silkworms, and the irregular sericin layer presents microcracks along the fiber surface, as shown in FIG1 . The tensile strength on such fibers varies from fiber to fiber due to differences in the sample (which may be referred to as defects), and therefore, the strength of silkworm fibers in this context cannot be defined by a single value. Therefore, a statistical distribution is needed to quantitatively address the dependence of fiber strength on its defect distribution.
[0190] In this regard, the Weibull distribution is often considered to be a suitable statistical model, since the distribution considers the lowest possible breaking strength of zero, i.e., the distribution is bounded, it provides an accurate approximation of failure even with small sample numbers, and the parameters of the distribution allow for relatively good shape flexibility. To report the strength distribution of individual fibers, the two-parameter Weibull distribution or the Weibull cumulative distribution function is often used:
[0191]
[0192] Where f(σ) is the probability of failure of the fiber under the applied stress (σ), α is the scale parameter of the distribution, which represents the average strength or characteristic strength of the fiber according to a distribution that depends on the stress configuration and the test sample size, and β is the shape parameter, which depends on the defect size and is a measure of the strength variability (higher β values mean lower strength variability) and therefore also a measure of the fiber reliability. To calculate the scale (α) parameter and shape (β) parameter of the distribution, the double logarithm of the Weibull equation can be applied as follows:
[0193]
[0194] ln[-ln(1-f(σ))]=βlnσ-βlnα (3)
[0195] Equation (3) is then plotted, yielding a linear plot of slope β. The Weibull scaling parameter (α) of the fiber is readily obtained from the intercept of this line, given by:
[0196] α=e (截距 / β) (4)
[0197] Examples of two-parameter Weibull distributions for different fibers are given in Figure 2F The graphical representation is shown in FIG.
[0198] In some embodiments, σ represents strength - how strong a material is under applied stress.
[0199] Embodiments of the present invention demonstrate formulations for non-thermal removal of sericin glue layers from silk fibroin fibers. The developed treatment improves fiber mechanics and thermal stability. The method also enables the acquisition of soluble silk of high purity and rheological properties similar to those of natural silk. In addition, the methods disclosed herein provide for determining accurate and precise mechanical properties of biological fibers such as silk, which accounts for the asymmetry and / or presence of defects in the fibers. The developed method is not only beneficial for the production of silk-based materials with customized properties, but also for the correct determination of the mechanical properties of asymmetric fiber materials made from natural and synthetic components. The methods of the present invention can be extended to other non-biological fibers.
[0200] Example 5
[0201] Calculation and Measurement of Weibull Distribution
[0202] One way to calculate accurate and precise mechanical properties is through the use of experimental and analytical methods together. The following is a step-by-step example of how to calculate the mechanical parameters of a fiber:
[0203] 1) Use an experimental device to measure the extension (mm) of a fiber relative to the load (N) until the fiber breaks. Perform this measurement on more than one fiber.
[0204] 2) For the purpose of comparing degumming processes, stage 1 was performed for different degumming treatments, for example at different molar concentrations and incubation media such as NaOH or Na2CO3 between 0M and 1M.
[0205] 3) Use confocal microscopy to take cross-sectional images of the fiber along its length. Typically, the fiber will be pre-dyed to distinguish between regions of different materials, such as fluorescence of materials with different extinction coefficients. As discussed above, confocal microscopy with subsequent processing can distinguish between fibroin regions and sericin regions. For completely degummed fibers, the sericin regions will be absent, negligible, or relatively small.
[0206] 4) The processing unit calculates the cross-sectional area of the fiber as a whole, the fibroin region, and the sericin region. The statistical analysis yields the mean cross-sectional area of each component of the fiber as well as the standard deviation of the data set.
[0207] 5) The average cross-sectional area (for any region in the fiber, or the total area) is then used to calculate the tensile stress relative to strain for each fiber (σ(MPa) = F / A = force (N) / area (m 2 )).
[0208] 6) The maximum strength (MPa) of each fiber was measured using a stress-strain curve. It is the maximum stress that a material can withstand when stretched or pulled before breaking. The standard deviation of this value was also obtained.
[0209] 7) Determine the Young's modulus (MPa) from the gradient of the stress-strain curve for each fiber. The Young's modulus for all fibers in the data set was then averaged. The standard deviation of this value was also obtained.
[0210] The method defined above can be further improved by using the statistical analysis tool, the two-parameter Weibull distribution, to more accurately and precisely define fiber mechanics. There are many versions of the Weibull distribution that define statistical analysis tools. Generally, in this case of mechanical properties of fibers, using more data points will produce lower standard deviations and more precise property results.
[0211] The following example demonstrates how to use the Weibull distribution:
[0212] - Collect stress / strain data sets for more than one fiber. For example purposes, at least five individual stress / strain curves may be used;
[0213] - Extract the maximum strength of each fiber from these data sets as above;
[0214] - Sort the maximum intensities from lowest to highest using an index n (n=1, 2, 3, ...), where n=1 is the lowest;
[0215] - Calculate the natural logarithm of the maximum intensity, i.e. ln(intensity max );
[0216] - Calculate the failure probability f(σ) as follows: f(σ) = (n-0.5) / n max , where n is the number of (sorted) fibers in the data set, and n max is the number of the highest maximum intensity;
[0217] - Plotting the natural logarithm of the maximum intensity versus ln(-ln(1-f(σ)) provides a Weibull distribution;
[0218] - The above figure gives a linear distribution, where β is the gradient and α is calculated by α=exp(intercept / β).
[0219] Example 6
[0220] Silk fibroin extraction
[0221] Extraction of silk fibroin from Bombyx mori cocoons is carried out as follows. The cocoons are chopped and then boiled in a 20 mM sodium carbonate (≥99.5%, Fischer Chemical, USA) solution at a ratio of 200 mL solution per gram of raw cocoon. This process produces degummed fibers. The degummed fibers are then washed and dried and subsequently desolvated at 60° C. in a concentrated aqueous lithium bromide solution. The resulting solution is centrifuged and dialyzed against Milli-Q water. In some embodiments, dialysis is performed to remove LiBr from the solution. In one embodiment, after dialysis, the solution does not contain LiBr.
[0222] In some embodiments, after dialysis, the dissolved fiber component is dialyzed again for salt solution.Such additional dialysis results in the introduction of desired salt into the reconstructed silk fibroin solution.In one embodiment, adding salt such as CaCl2, KCl, NaCl to the reconstructed solution enhances the mechanical properties of the reconstructed solution.In one embodiment, adding salt to the reconstructed solution enhances the mechanical properties of any fiber spun by such solution later or any material formed by the reconstructed solution.In one embodiment, adding salt to the reconstructed solution increases the viscosity of the solution.This may be advantageous for the properties of the fiber / material formed by the reconstructed silk protein solution.
[0223] In some embodiments, the present invention provides a process for preparing a reconstructed silk fibroin solution, the process comprising at least a portion of the steps described above. For example, in one embodiment, salt is added to the reconstructed solution after removing LiBr. In another embodiment, salt is not added to the reconstructed solution after removing LiBr. In one embodiment, salt is added using dialysis. In one embodiment, salt is added without dialysis. In one embodiment, salt is added from a solid salt. In one embodiment, salt is added from a salt solution. In some embodiments, dialysis is carried out between 1 hour and 5 hours. In some embodiments, dialysis is carried out between 5 hours and 10 hours. In some embodiments, dialysis is carried out between 1 day and 2 days. In some embodiments, dialysis is carried out between 1 day and 5 days. In some embodiments, dialysis is carried out between 3 days and 4 days.
[0224] In some embodiments, the silk fibroin of reconstruction refers to the liquid comprising independent silk fibroin and water.In some embodiments, the silk fibroin of reconstruction is the solution in which the silk fibroin is completely soluble.In some embodiments, the silk fibroin of reconstruction is in the form of suspension.In some embodiments, the aggregate of silk fibroin is present in the silk fibroin solution of reconstruction.In some embodiments, stabilizer is added to the silk fibroin solution of reconstruction.
[0225] In some embodiments, the resulting silk fibroin material is in liquid form. In some embodiments, the silk fibroin material is dissolved in water or a solution so that separate silk fibroin is present in the water or the solution.
[0226] In one embodiment, the invention provides a process for producing a silk protein solution, the process comprising providing silk fibers degummed in a hydroxide solution as described herein, and dissolving the silk fibers in a salt solution.
[0227] In one embodiment, the salt solution comprises a salt selected from the group consisting of LiBr, ZnCl2, CaCl2, Ca(NO3)2, and LiSCN. In one embodiment, the solvent of the salt solution is selected from the group consisting of water, methanol, ethanol, or any mixture or combination thereof.
[0228] In one embodiment, after dissolving the fibers in the salt solution, the resulting solution is centrifuged and dialyzed against water to remove the salt. In one embodiment, the salt removal is complete. In one embodiment, only a portion of the salt is removed.
[0229] In one embodiment, after removing the salt by dialysis, the salt is reintroduced into the solution. According to this aspect and in one embodiment, the introduced salt is selected from (but not limited to): CaCl2, KCl, NaCl or any combination thereof. In one embodiment, the salt addition at this stage enhances the mechanical properties of the solution. In one embodiment, the silk protein solution is a reconstructed silk protein.
[0230] In one embodiment, the fibers are used for optical and / or mechanical property measurements as described herein before dissolving the degummed fibers in a salt solution.As described herein, hydroxide degumming is performed in embodiments of the invention rather than sodium carbonate degumming.
[0231] Example 7
[0232] Confocal microscopy
[0233] 3D images were taken by a Zeiss LSM 800 confocal imaging system (Carl Zeiss AG, Germany) with a Plan-Apochromat 20x / 0.8M27 (FWD=0.55mm) objective for confocal imaging. At least five 3D images were taken from each sample: natural silk fibers and degummed fibers treated differently with Na2CO3, NaOH 0.1M, NaOH 0.5M, and NaOH 1M. In brief, the samples were incubated with Nile red (with a final concentration of 3 μM) at room temperature for 16 hours, and then placed on a slide, and then covered and sealed with a cover glass. The conditions for the images were: excitation with Led lasers at 559nm (Nile red excitation) and 346nm (intrinsic fluorescence), and emission at 636nm (Nile red) and 442nm (intrinsic fluorescence). 90 Z stack slices (~33 μm) were taken, and the resolution was about 0.105×0.105×0.37 μm / pixel. 3D images were reconstructed by using Imaris software. In addition, 3D images were post-processed by a script of Matlab software to calculate the cross-section of the fiber. Fig.12 A schematic representation of the z-stack along the fiber is shown.
[0234] Example 8
[0235] Tensile test
[0236] The example of the experimental device for tensile test is provided below.Usually, tensile test is carried out by fixing the sample at two ends under controlled tension until failure.In this case, for example, the fiber is fixed at either end with a clamp, wherein the clamp is separated at a controlled speed until the fiber tears, breaks (fracture), breaks (break) and / or ruptures.The experimental device can vary from experiment to experiment.In some embodiments, the experimental device can be a system including mechanics and electrical equipment, a computer, a processing unit and a display unit, which measures the extension of the thread relative to the applied load.In other embodiments, such a system can input and output data related to the mechanical properties of the measured fiber and / or material.In some embodiments, the experimental device measures the mechanical properties of more than one fiber.
[0237] Depending on the nature of the sample measured, some of the following mechanical properties can be measured and obtained: Young's modulus, Poisson's ratio, yield strength, strain hardening, rupture, necking, ultimate strength, etc.
[0238] Single fiber samples for tensile testing were prepared by gluing untreated silkworm fibers and treated silkworm fibers produced by silkworms on a windowed paper frame with a gauge length of 20 mm. The samples were taken from the middle layer of three different silkworm cocoons. The quasi-static tensile test of the single fiber was carried out at a strain rate of 1 mm / min at room temperature using an Instron 5965 universal testing machine (UK) equipped with a 10N load cell. A fiber clamp was used to fix the paper frame on the instrument, and the side edges of the frame were cut off before testing. As specified in Table 2, a minimum of 17 fibers were tested for each sample, and tensile properties (Young's modulus, strength, and breaking strain, etc.) were calculated from the elevated stress-strain curves based on the cross-sectional area of each fiber as obtained in Figure 6. These figures are based on the following: Figure 2A The cross-sectional area of each fiber group obtained in was calculated in the form of true stress-true strain curve, and the tensile properties (Young's modulus (E), tensile strength (σ t ) and fracture strain (ε t )). All quantitative mechanical results are expressed as mean ± standard deviation (SD). One-way analysis of variance (ANOVA) was performed using OriginPro 2022 software to determine whether there were significant differences between the mean values of the experimental groups, such as Fig.13 The differences between the groups were statistically significant at p < 0.05.
[0239] Example 9
[0240] Bulk FT-IR spectroscopy measurement
[0241] Fourier transform infrared (FT-IR) spectra of the whole regenerated silk fibroin were obtained using a Nicolet iS50 FT-IR spectrometer equipped with an ATR Smart iTX (attenuated total reflectance) accessory with a resolution of 4 cm -1 , and 32 separate scans were performed for each measurement.
[0242] At least three measurements were performed for each sample, and the spectra were normalized and averaged. Seven peaks were selected for fitting analysis; intermolecular β-sheet (1609 cm -1 、1621cm -1 and 1631cm -1 ), α-helix / random coil (1650cm -1 ), β-angle (1673cm -1 ) and antiparallel amyloid β-sheets (1695 cm -1 and 1703cm -1 ).
[0243] Example 10
[0244] IR spectroscopy analysis
[0245] At ~1720cm -1 -1600cm -1 All IR spectra (integral FT-IR and nano-IR) between 1 and 2 were linearly baselined to cover the amide I region. To resolve the secondary structure of the samples, the spectra were normalized and averaged. Then, seven Gaussian peaks (1609 cm -1 、1621cm -1 、1631cm -1 、1650cm -1 、1673cm -1 、1695cm -1 and 1703cm -1 And the degree of freedom is 2cm -1 ) The spectra were fitted (using OriginPro 2019b 64bit software). The fitting analysis of all spectra has reached fitting convergence, and the Chi-Sqr tolerance value is 1E -6 The secondary structure of these peaks is explained as follows: 1609 cm for the intermolecular β-sheet -1 、1621cm -1 and 1631cm -1 , 1650 cm for α-helix and random coil -1 , β-angle is 1673cm -1 and the antiparallel amyloid β-sheet is 1695 cm -1 and 1703cm -1 .
[0246] Embodiment 11
[0247] High-resolution scanning electron microscopy (HRSEM) analysis
[0248] HRSEM images were obtained using Ultra-55 and SIGMA ultra-high resolution SEM (Carl Zeiss, Germany).The samples were placed on an aluminum stub and fixed with carbon tape.
[0249] Example 12
[0250] X-ray diffraction (XRD) spectrum
[0251] XRD of the crystalline structures associated with the silk I and silk II polymorphisms present in silk fibroin fibers was performed in reflection geometry using a TTRAX III (Rigaku, Japan) θ-θ diffractometer with a rotating Cu anode operating at 50 kV and 200 mA. The curved graphite monochromator and PMT detector were aligned in the diffracted beam, and θ / 2θ scanning was performed under mirror conditions in Bragg-Brentano mode with a variable slit. The 2θ scanning range was 1 degree to 80 degrees, with a step size of 0.025 degrees and a scanning speed of 0.4 degrees per minute.
[0252] Example 13
[0253] Gel electrophoresis (SDS-PAGE)
[0254] 25 μg of silk fibroin sample was loaded and run on a gradient gel (4%-20%) from Geba using the manufacturer's protocol. Coomassie protein stain (ISB1L) (ab119211) was stained overnight and washed with water for several hours.
[0255] Embodiment 14
[0256] Silkworm anatomy
[0257] The 5th instar silkworm larvae were anesthetized with N2 for 15 min, and then rapidly dissected by removing the head and applying a longitudinal dorsal incision. The silk glands were gently extracted and rinsed with Mili-Q water, and then gently placed on a slide (25 mm×16 mm), which was then set on a microscope stage for microscopic examination.
[0258] Embodiment 15
[0259] Rheological analysis
[0260] Rheological characterization was performed at 25 °C using a HR-20 Discovery hybrid rheometer (TA Instruments, US) using a 40 mm diameter aluminum parallel plate geometry. The geometry was lowered to a gap of 100 μm at the slowest possible speed. A small amount of distilled water was applied around the sample and the area was closed with a loose-fitting lid to avoid drying and skin formation. The sample was initially heated for 1 s. -1 The constant shear rate shear was continued for 100 seconds to evenly distribute the liquid and remove any residual stresses due to previous handling of the sample. Next, an oscillatory frequency test was performed at a strain of 0.02 (within the linear elastic region of the material) and an angular frequency of 100 rad / s to 0.1 rad / s. The sample was then subjected to two repeated flow sweep test steps, each consisting of a 100 rad / s to 200 rad / s flow sweep test. -1 Increase to 500s -1and from 500s -1 Reduced to 0.1s -1 The final step consists of a second oscillation frequency test with the same parameters as before.
[0261] Example 16
[0262] Structural characteristics and mechanism of silk fiber degumming
[0263] To further understand the structural origin of the increased mechanical strength of NaOH-treated silk fibers compared to standard treatment, Fourier transform infrared spectroscopy (FT-IR) analysis was performed, in which changes in the secondary structure of silk proteins were evaluated. Typically, the vibrational spectrum of proteins / peptides is characterized by two major bands, namely, amide I (1600 cm -1 -1700cm -1 ) and amide II (1480 cm -1 -1600 cm -1 ), which correspond to C=O and NH bending / CH stretching, respectively. The results summarized in Figure 14 highlight the existing changes between the protein FTIR spectra obtained from the degummed fibers. The Na2CO3 degummed fibers contained 27% α-helices and random coils and 4.5% β-turns, while the fibers degummed using the NaOH procedure contained 20%-24% and 8.7%-12.4%, respectively. The β-sheet level of the fibers degummed in all procedures was similar, ranging from 66.7% to 68.7% (Figure 14). The slight changes in secondary structure between the degummed fibers led us to test additional features of the level of interactive bonding between the fibril bundles that make up the fibers. Therefore, dynamic mechanical analysis (DMA) was performed to measure the glass transition (Tg) and crystallization level of the fibers. The crystallization level of 0.1M and 0.5M (NaOH) was higher than that of standard degumming. In addition, the Tg of 0.1M and 0.5M (NaOH) was at a higher temperature than that of standard degumming, which indicated the strong hydrogen bonding between the amide groups in the adjacent protein chains in their amorphous structures. These results indicate that the 0.1M and 0.5M degummed fibers contain hydrogen bonds in their amorphous structures and the β-sheet structure is more stable and stronger (see Fig. 10A , Fig. 10B ).
[0264] X-ray analysis is carried out to detect the difference of the crystallization fraction of the treated fiber, and gel electrophoresis is carried out to check the integrity of the protein molecule. Generally, the silk fibroin constituting the silk fibroin fiber exists mainly in crystalline or amorphous (random coil) form. The fine balance between these two forms (most of the crystalline components are decorated with a small portion of disordered regions) defines the special mechanical properties of the fiber. XRD analysis shows that 2θ has characteristic diffraction peaks at 9.5 °, 20.7 °, 24.3 ° and 39.7 ° (corresponding crystal spacing is and like Figure 4B The β-sheet crystal structure of silk II is indicated by the diffraction peaks at 12.2°, 19.7°, and 24.7° (corresponding to the crystal spacing of and ) indicates a disordered random coil silk protein structure I. Interestingly, and The diffraction peak of is not present in the Na2CO3 treated sample, indicating a decrease in both the crystalline and disordered fractions of the protein.
[0265] In order to further examine the integrity of the silk fibroin molecules as a function of the applied treatments, electrophoretic protein gel analysis was performed. In detail, denaturing gels have been used to test the presence of heavy and light chain protein subunits. β-mercaptoethanol (a chemical component used in electrophoretic gel analysis) is able to destroy disulfide (SS) bridges via a reduction reaction, denaturing proteins and thus providing additional information about protein chains. Figure 4A The results summarized in revealed the absence of light chain subunits in samples degummed using the standard Na2CO3-based protocol, whereas for NaOH-treated samples, the presence of both heavy and light chain protein subunits had been observed. Such observations point to the effectiveness of the NaOH-based degumming method for gently removing the glue components without destroying the protein units.
[0266] SAXS analysis of soluble silk fibroin from the standard Na2CO3-based protocol compared to NaOH-treated samples. The results from the Na2CO3-based protocol contained very few nanocompartments and more slabs compared to the NaOH-treated samples. Nanocompartments are a method to stabilize soluble silk fibroin in the silkworm glands. SAXS analysis of native silk fibroin (taken directly from the silkworm glands) demonstrated very similar behavior to the NaOH-treated samples ( Fig.11A and Table 4).
[0267] Figure 4A Gel electrophoresis analysis of silk fibroin molecules is shown. Fig.11A Small angle x-ray scattering (SAXS) analysis of soluble silk fibroin is shown; the azimuthal interaction background-subtracted solution X-ray scattering absolute intensity I is shown as a function of the size of the scattering vector q from native silk and soluble RSF obtained from different degumming methods.
[0268] The model combinations used to fit the SAXS data are shown in Table 4. The model type (sphere, disk or plate), model radius R, polydispersity of the radius (ΔR), height of the disk or plate, and mass fraction of the model are shown.
[0269] Table 4
[0270]
[0271] Fig. 11B and Fig. 11C Rheological analysis showing the change in viscosity in response to applied shear, where the shear rate changes from 0.1 s -1 Increase to 500s -1 and from 500s -1 Back to 0.1s -1 The following samples were analyzed: RSF solution obtained by chemical redissolution of degummed silk fibers in the presence of Na2CO3 and NaOH 0.5M. The figure shows 1( Fig. 11B ) and 100( Fig. 11C ) with standard deviation (mean ± sd, n ≥ 3).
[0272] Embodiment 17
[0273] Rheology and structural hierarchy of degummed silk fibroin fibers
[0274] To illustrate the effect of different degumming procedures on the rheological behavior of reconstructed silk fibroin (RSF) fluids, the viscosity change in response to applied shear was measured, where the shear rate was increased from 0.1 s -1 Increase to 500s -1 and from 500s -1 Reduced back to 0.1s -1 A comparison between the rheological properties of RSF obtained via different degumming protocols followed by chemical re-dissolution and native silk fibroin (NSF) extracted directly from the silk gland of Bombyx mori via dissection is shown. The viscosity values recorded for RSF solutions (obtained following a protocol including degumming steps in the presence of 0.5 M NaOH and 1 M NaOH) are significantly higher than those obtained via the standard degumming protocol ( Figure 3C ). Such values are comparable to those of natural silk. At the maximum shear rate (500s -1 ), the viscosities of the silk solutions reconstituted from fibers degummed with 0.5 M NaOH and 1 M NaOH were 0.03 Pa.s and 0.05 Pa.s, respectively. However, the viscosity of the solution reconstituted from fibers degummed with 0.1 M NaOH was 0.03 Pa.s and 0.05 Pa.s, respectively. -1 The shear rate is 0.25Pa.s. At the minimum shear rate (0.1s -1), the viscosities of the RSF solutions (0.5M NaOH and 1M NaOH degumming steps) were 501.17 Pa.s and 644.53 Pa.s, respectively, and for 0.1M NaOH, the viscosity was 374 Pa.s. In contrast, the RSF of the fiber derived from the degumming using NaOH 0.1M was higher than that of the Na2CO3 (for 500s -1 The shear rate obtained was 0.027 Pa.s, and for 0.1s -1 The shear rate, the value obtained was 285.5 Pa.s), but it was not significant. This observation could be explained by the insufficient NaOH concentration to effectively remove the glue layer, which further affects the quality of the RSF solution, similar to Na2CO3.
[0275] Embodiment 18
[0276] Dynamic Mechanical Analysis (DMA)
[0277] DMA tests were performed on a TA Q850 in DMA multi-frequency strain mode. Standard polymer test parameters were used: (i) a temperature ramp rate of 3 °C / min, (ii) a frequency of 1 Hz, and (iii) 3 × 10 -3 N stress control. A preload force equivalent to 0.012N stress was applied to keep the test fiber in tension throughout the dynamic oscillation. Note that the temperature sweep is only shown as the temperature increases. The DMA program was performed over a full range temperature sweep from 27°C to +270°C (see Fig. 10A ).
[0278] Embodiment 19
[0279] Small angle X-ray scattering (SAXS) measurements
[0280] Solution SAXS measurements were performed at the ID02 beamline at the European Synchrotron Radiation Facility (ESRF) using a 32.4 × 145 μm 2 The beam size was 1000 nm (vertical and horizontal, respectively), the photon energy was 12.23 keV, the Eiger2 4M (Dectris AG) detector, the sample-to-detector distance was 3.114 m, and the exposure time was 0.1 s. The SAXS model was calculated by X+ software using 333 e·mm -3 The water electron density is . The data are fit to a uniform disk and to a linear combination of sphere and / or rod geometries.
[0281] Based on the intensity of each model at zero scattering vector and the contribution of each model’s volume, we calculated Fig.11AThe mass fractions of disks (0.9871), spheres (0.0003), and fibrils (0.0126) in the modeled red curve presented in FIG.
[0282] Embodiment 20
[0283] Cross-sectional and volumetric analysis of degummed silk fibroin fibers - establishing 'true' values
[0284] Before evaluating the mechanical properties of silk fibers treated with the newly developed NaOH-based formulation, it is necessary to determine the cross-sectional area and volume parameters of the fibers, which will be further incorporated into the calculations. In order to measure the cross-sectional area of the fibers and calculate the volume of the fibers, the present disclosure combines the above-mentioned fluorescence assays (intrinsic fluorescence and Nile red staining) with confocal microscopy analysis ( Figures 1A to 1D ) and image processing technology ( Figure 1C and Figure 1D , Figure 11). Thousands of z-stack confocal images were collected (see Table 5) and further post-processed into reconstructed 3D models ( Figure 1C and Figure 1D ).
[0285] Table 5
[0286]
[0287] In order to infer the cross-sectional parameters of the silk fiber components, the post-processing analysis images were converted into binary format using MatLab scripts to calculate the cross-sectional area of each component alone and in combination. The values obtained were then used for mechanical calculations, which are described in detail herein. The cross-sectional analysis shows that the inconsistent and large STD of the silk fibers degummed in the presence of Na2CO3 (see Fig. 6A and Table 5), while the narrowest STD was reported for NaOH 0.5 M treatment (Fig. 6c and Table 5). Such differences may be due to the better solubility of sericin component in NaOH and the absence of thermal damage in silk fibroin fibers.
[0288] A summary of the synergistic analysis of the measured cross-sectional areas of untreated fibers, fibers degummed via standard methods, and silk fibroin fibers treated with NaOH-based solutions is given in Figure 2A , Fig. 6F and are depicted in Table 5. The analysis indicated that there were differences in the effectiveness of sericin removal between the standard method and the developed NaOH-based formulation. At high NaOH molar concentrations (1 M), events of disintegration of micron-sized bundles into individual nanofibrils were observed (see Figure 7). Figure 2A , Fig. 6FAnalysis of the measured cross-sectional areas shown in and Table 5 revealed that NaOH (0.5 M) based degumming resulted in the smallest standard deviation (STD) values and an almost complete overlap between the values obtained from the confocal microscopy analysis.
[0289] Those skilled in the art to which the present invention pertains will readily appreciate that numerous changes, variations and modifications may be made, mutatis mutandis, without departing from the scope of the subject matter disclosed herein.
Claims
1. A method for removing at least a portion of a glue layer from a silk fiber, the method comprising: incubating the silk fibers in an incubation medium, the incubation medium comprising a hydroxide; The method is carried out at a temperature in the range of 5 degrees Celsius to 60 degrees Celsius.
2. The method of claim 1, wherein the incubation medium consists of a hydroxide and water. The method according to claim 1 , wherein the incubation consists of a single incubation step.
4. The method according to claim 1, wherein the hydroxide is selected from: NaOH, LiOH, KOH, RbOH, CsOH, Ca(OH)2, Sr(OH)2 or Ba(OH)2 or a combination thereof.
5. The method according to any one of claims 1 to 4, wherein the concentration of the hydroxide in the incubation medium is in the range between 0.1 M and 1 M.
6. The method according to any one of claims 1 to 5, wherein the incubation medium further comprises at least one buffer.
7. The method according to any one of claims 1 to 6, wherein the incubation medium further comprises at least one salt.
8. The method according to any one of claims 1 to 7, wherein the incubation is performed for between 1 minute and 60 minutes.
9. The method of any one of claims 1 to 8, further comprising rinsing the silk fibers in a liquid after the incubating.
10. The method of claim 9, wherein the liquid comprises water or a solution.
11. The method of claim 9 or 10, further comprising drying the silk fibers after rinsing in the liquid.
12. The method of any one of claims 1 to 11, further comprising separating the silk fibers into individual fibers.
13. A degummed silk fiber comprising a core and a glue layer, wherein the glue layer constitutes 0% to 20% of the cross-sectional area of the degummed silk fiber.
14. The degummed silk fiber according to claim 13, wherein the fiber exhibits a Young's modulus of at least 10 GPa.
15. The degummed silk fiber of claim 13, wherein the fiber exhibits a Young's modulus at least 1.5 times greater than that of untreated silk fiber.
16. The degummed silk fiber of claim 13, wherein the fiber exhibits a tensile strength of at least 400 MPa.
17. The degummed silk fiber of claim 13, wherein the fiber exhibits a tensile strength at least 1.25 times greater than that of untreated silk fiber.
18. The degummed silk fiber of claim 13, wherein the fiber exhibits a strain at break of at least 0.
2.
19. The degummed silk fiber of claim 13, wherein the fiber exhibits a Weibull characteristic strength parameter (α) of at least 400 MPa.
20. The degummed silk fiber of claim 13, wherein the fiber exhibits a Weibull characteristic intensity parameter (a) at least 1.2 times greater than that of untreated silk fiber.
21. The degummed silk fiber of claim 13, wherein the fiber exhibits a Weibull shape parameter (β) of at least 4.
22. The degummed silk fiber according to claim 13, wherein the degummed silk fiber is produced by the method of any one of claims 1 to 12.
23. A reconstructed silk fibroin material, comprising silk fibroin and a liquid, wherein the silk fibroin is derived from the degummed silk fiber of any one of claims 13 to 22.
24. The reconstructed silk fibroin material of claim 23, wherein the liquid comprises water.
25. The reconstructed silk fibroin material of claim 23, wherein the liquid comprises a saline solution.
26. The reconstructed silk fibroin material of claim 23, wherein the liquid is an aqueous solution comprising a salt selected from CaCl2, KCl, NaCl, or any combination thereof.
27. A method for determining average mechanical properties of more than one asymmetric fiber, the method comprising: a. obtaining more than one cross-sectional image along the length of one of the asymmetric fibers using a confocal microscope; b. Calculate the cross-sectional area of the asymmetric fiber; c. calculating the average cross-sectional area along the length of the asymmetric fibers; d. measuring the extension of the asymmetric fiber relative to the load until the asymmetric fiber breaks; e. using the average cross-sectional area to obtain the stress-strain diagram of the asymmetric fiber; f. obtaining the maximum strength and Young's modulus from the stress-strain diagram of the asymmetric fiber; g. performing stages 'a' to 'f' on more than one asymmetric fiber to obtain more than one stress / strain data set; and h. Calculate the average maximum strength and average Young's modulus of the more than one asymmetric fibers.
28. The method of claim 27, further comprising utilizing a two-parameter Weibull distribution, comprising: a. sorting the maximum intensity of the more than one stress / strain data sets from lowest to highest and assigning a number to the data sets; b. calculating the natural logarithm of the maximum intensity of each of the data sets; c. Calculate the failure probability f(σ) of each of the data sets; d. Plotting the natural logarithm of the maximum intensity versus ln(-ln(1-f(σ)); and e. From the graph of 'd', the shape parameter β is extracted from the gradient and the scale parameter α is extracted from α=exp(intercept / β).
29. The method of claim 27, wherein the asymmetric fibers are dyed with a dye prior to step (a).
30. The method of any one of claims 27 to 29, wherein the asymmetric fibers are of biological origin.
31. A method according to any one of claims 27 to 30, wherein the asymmetric fibres are degummed.
32. A method according to any one of claims 27 to 31 wherein the asymmetric fibres are coated with an additional material.